Metallic pigment composition
By using composite particles in metal pigments, the problem of corrosion of metal coatings in water-based coatings is solved, and high stability, excellent color and adhesion are achieved.
Patent Information
- Application Number
- CN202411897180.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-26
- Filing Date
- 2022-03-25
- Publication Date
- 2025-03-25
AI Technical Summary
Existing metal coatings are prone to corrosion in water-based coatings, resulting in reduced color tone of coatings, poor storage stability and poor adhesion of coatings.
A metal pigment composition containing composite particles is used, which consists of metal particles and a silicon-containing compound layer of more than one layer formed on the surface. By controlling the shape of the particles, the particle size distribution and the thickness of the cover layer, the stability and color of the coating are improved.
It significantly improves the stability, storage stability and film tone of the paint, ensures the adhesion between the paint and the substrate, and meets the needs of high light brightness, different color sense and concealment with the angle.
Smart Images

Figure BDA0005202168440000551
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of March 25, 2022, application number 202210305319.X, and invention name “Metallic Pigment Composition”. Technical Field
[0002] The present invention relates to a novel metal pigment composition containing composite particles. More specifically, the present invention relates to a novel metal pigment composition containing composite particles having excellent coating stability, storage stability, coating film color tone (specifically, brightness, flip flop, hiding power), and coating adhesion. Background Art
[0003] Conventionally, metallic pigments have been used for metallic paints, printing inks, plastic kneading, etc., in order to obtain cosmetic effects that emphasize metallic texture.
[0004] In recent years, in the field of coatings, as a resource-saving and pollution-free countermeasure, the necessity of converting to water-based coatings with less organic solvent usage has increased, but for metallic coatings containing metallic pigments, the types of water-based coatings that can be actually used are still insufficient. As a reason for this, it can be cited that metallic pigments are easily corroded in water-based coatings. When metal powders are present in water-based coatings or water-based inks, based on the properties of various metals, corrosion caused by water occurs and hydrogen is generated in any one or more ranges of acidity, neutrality, and alkalinity. In particular, it is an extremely serious safety issue in the manufacturing process of coatings and inks by coating manufacturers and ink manufacturers; in the coating process and printing process of automobile, home appliance manufacturers, printing manufacturers, etc.
[0005] In addition, since the corrosiveness of the metallic pigment becomes a problem in terms of storage stability, the corrosion resistance of the metallic pigment can be alternatively referred to as storage stability.
[0006] In addition, the smoothness of the metal surface is lost due to corrosion, so it is inevitable that the color tone when used as a coating film, that is, the coating film color tone (specifically, brightness, angle-shifting color, hiding power) will be reduced. In addition, due to the diversification of color designs in recent years, there is a high demand for metallic coatings with high glossiness. Therefore, as a coating film color tone, there is currently a desire for high angle-shifting color (that is, the property of brightness changing according to the viewing angle, a parameter that depends on the degree of orientation of the metallic pigment).
[0007] When a metallic pigment is used as a paint, it is required that the aggregation of the pigment (specifically, the aggregation of particles constituting the pigment) is small, that is, the paint has stability.
[0008] Furthermore, when a metallic pigment is formed into a coating film by coating, it is required that the adhesion to the substrate, that is, the coating adhesion, does not decrease.
[0009] Patent document 1 (International Publication No. 2020 / 21735 Pamphlet) discloses a coated resin metal pigment having a small average particle size in which a specified copolymer is used as a coating resin in order to solve the problem of low adhesion with the resin in the coating film when aluminum pigments that have not been surface treated are formed into coatings or printing inks.
[0010] In addition, Patent Document 2 (International Publication No. 2019 / 77904 Pamphlet) discloses an aluminum flake pigment containing small-diameter aluminum flakes with a particle size of less than 1 μm from the perspective of providing new design and high-grade metallic feel, wherein the ratio of the number of the small-diameter aluminum flakes to the total number of the above-mentioned aluminum flakes in the microscope image observed using a scanning electron microscope is less than 35%.
[0011] However, it is difficult to provide the above-mentioned coating stability, storage stability, coating film color tone (specifically, brightness, angular color change, hiding power), and coating adhesion that are sufficiently satisfactory using any of the technologies disclosed in these patent documents, and the current situation is that the development of a new type of metal pigment composition containing composite particles is desired.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: International Publication No. 2020 / 21735 Pamphlet
[0015] Patent Document 2: International Publication No. 2019 / 77904 Pamphlet Summary of the invention
[0016] Problem that the invention aims to solve
[0017] An object of the present invention is to provide a novel metal pigment composition containing composite particles which is not available in the prior art.
[0018] A further object of the present invention is to provide a novel metal pigment composition containing composite particles which solves the problems of the prior art, namely, is excellent in coating stability, storage stability, coating film color tone (specifically, brightness, color flop, hiding power), and coating adhesion.
[0019] Solutions for solving problems
[0020] The present inventors have conducted intensive research and have found that the above-mentioned problems can be solved by a metal pigment composition as follows: the metal pigment composition comprises composite particles, the composite particles comprising metal particles and a coating layer comprising one or more silicon-containing compound layers (i.e., silicon dioxide layers) on the surface thereof, the composite particles forming a scaly shape, the composite particles being coated so that the average thickness of the composite particles (specifically, the size (particle diameter) of the metal particles serving as the core of the composite particles and the thickness of the silicon dioxide layer constituting the coating layer on the surface thereof) is within a certain range, and the volume-based D in the particle size distribution of the composite particles is controlled. 50 The ratio of the silicon content of the silicon dioxide layer to the metal element content of the metal particles as the core particles of the composite particles and the number ratio of the composite particles having a predetermined fine particle size are controlled within a predetermined range.
[0021] In addition, the present inventors have found that the metal pigment composition can also solve the following problems: in the case where a covering layer including one or more silicon compound layers (i.e., silicon dioxide layers) is formed on the surface of the metal particles serving as the core of the composite particles contained in the metal pigment composition, a silicon dioxide layer of a certain thickness is required to exert corrosion resistance; on the other hand, if the size (particle diameter) of the composite particles becomes increasingly small, the metal particles serving as the core also become smaller, and thus the thickness of the silicon dioxide layer increases relatively, the orientation of the metal pigment is hindered, and it is difficult to exert the original optical properties of the metal particles; if the size (particle diameter) of the composite particles becomes increasingly small, the adhesion between the substrate and the coating is hindered, thereby reducing the adhesion of the coating resin substrate, etc.
[0022] That is, various aspects of the present invention are as follows.
[0023] [Method 1]
[0024] A metallic pigment composition comprising composite particles, wherein the composite particles have metallic particles and one or more covering layers on the surface of the metallic particles.
[0025] (1) The composite particles are scaly in shape,
[0026] (2) The volume-based D when the particle size distribution of the composite particles is measured using a laser diffraction particle size analyzer 50 is 3 μm or more and 30 μm or less,
[0027] (3) the average thickness of the composite particles is 20 nm or more and 300 nm or less,
[0028] (4) at least one of the aforementioned covering layers is a layer containing a silicon compound,
[0029] (5) the ratio of the metal element content based on the metal particles in the composite particles to the silicon content based on the coating layer is 0.02 or more and 0.3 or less in terms of the ratio of the silicon content to the metal element content,
[0030] (6) The number ratio of the composite particles having a particle size of 0.1 μm or more and 1 μm or less relative to the total number of the composite particles in the metal pigment composition is 10% or less.
[0031] [Method 2]
[0032] The metallic pigment composition according to the above-mentioned [Aspect 1], wherein the volume-based D when the particle size distribution of the composite particles is measured using a laser diffraction particle size analyzer is 50 The ratio of the number of the composite particles having a particle size three times or more of the size of the composite particles is 3% or less relative to the total number of the composite particles in the metallic pigment composition.
[0033] [Method 3]
[0034] The metallic pigment composition according to [Aspect 1] or [Aspect 2], wherein the metal particles are aluminum or an aluminum alloy.
[0035] [Method 4]
[0036] The metallic pigment composition according to any one of [Aspect 1] to [Aspect 3], further comprising a coating layer containing at least one of a metal, a metal oxide, a metal hydrate and a resin.
[0037] [Method 5]
[0038] The metallic pigment composition according to any one of [Aspect 1] to [Aspect 4], wherein the silicon compound-containing layer is disposed at least as an outermost layer.
[0039] [Method 6]
[0040] A water-based metallic paint comprising the metallic pigment composition according to any one of [Aspect 1] to [Aspect 5] above.
[0041] [Method 7]
[0042] A water-based metallic coating film comprising the metallic pigment composition according to any one of [Aspect 1] to [Aspect 5] above.
[0043] Effects of the Invention
[0044] According to the present invention, it is possible to provide a novel metal pigment composition containing composite particles which is not available in the prior art.
[0045] According to a preferred embodiment of the present invention, a metal pigment composition can be provided which is excellent in coating stability (specifically, the property that the particles constituting the pigment are less likely to aggregate with each other when the pigment is used as a coating), storage stability (specifically, the property that the generation of hydrogen gas due to corrosion can be suppressed), coating film color tone (specifically, the property that the brightness, angle-dependent color sense, and hiding power are high), and coating adhesion (specifically, the property that the metal pigment is coated to form a coating film with high adhesion to the substrate). DETAILED DESCRIPTION
[0046] The present invention will be described below based on typical or preferred embodiments, but the present invention is not limited to these embodiments. Unless otherwise specified, these embodiments can be freely combined within the scope of the present invention defined in the appended claims.
[0047] 1. Composite particles contained in the metal pigment composition
[0048] The metallic pigment composition of the present invention comprises composite particles having metal particles and one or more covering layers on the surface of the metal particles.
[0049] In this specification, the term "metallic pigment composition" refers to a composition in which composite particles containing metal particles and one or more covering layers on the surface of the metal particles are dispersed in a solvent containing water and / or a hydrophilic solvent, or the composite particles together with a solvent containing water and / or a hydrophilic solvent, and may contain other components arbitrarily selected.
[0050] In the present specification, a composition obtained by adding a resin to a metal pigment composition may be referred to as a "resin composition" or a "resin composition containing a metal pigment composition" in distinction from the term "metal pigment composition".
[0051] Metal particles
[0052] The composite particles contained in the metal pigment composition of the present invention include metal particles and one or more coating layers formed on the surface of the metal particles. That is, the metal particles serving as the core of the composite particles have one or more coating layers formed on the surface of the metal particles.
[0053] The material of the metal particles (core particles) constituting the composite particles is not particularly limited, and may be any metal used as a known or commercially available metal pigment, such as aluminum, aluminum alloy, zinc, iron, magnesium, nickel, copper, silver, tin, chromium, stainless steel, etc. In this specification, the metal constituting the metal particles of the composite particles includes not only a metal single substance but also an alloy and an intermetallic compound.
[0054] As described above, the metal particles may be made of a metal composed of only one metal element alone, or may be made of a combination of two or more metals composed of only one metal element (ie, metals composed of two or more metal elements).
[0055] The metal particles in the present invention are preferably metals containing aluminum as a main component, for example, preferably aluminum or an aluminum alloy, more preferably aluminum.
[0056] There is no limitation on the shape of the metal particles, but scaly (thin flakes) are particularly preferred. Thus, the composite particles contained in the metal pigment composition of the present invention may also have a scaly shape, and as a result, high concealment can be obtained more reliably. From the above viewpoint, the diameter-to-thickness ratio (shape coefficient obtained by dividing the average particle diameter by the average thickness) of the scaly metal particles is preferably greater than 20 and less than 30. By having a diameter-to-thickness ratio of the metal particles of greater than 20, a higher glossiness can be obtained. In addition, by having a diameter-to-thickness ratio of the metal particles of less than 3000, the mechanical strength of the flakes is maintained, and a stable color tone can be obtained. Here, the average thickness of the metal particles used in the present invention can be calculated from the water surface diffusion area and density of the metal particles.
[0057] The average particle size of the metal particles is sufficient to achieve the particle size distribution of the composite particles described below. 50 The average particle size is not particularly limited. That is, it is preferred to use D when the volume distribution is measured by a laser diffraction particle size distribution meter in the composite particles. 50 The average particle size of the metal particles is set to be 3 μm or more and 30 μm or less.
[0058] The average particle size of the metal particles can be controlled by appropriately adjusting the particle size of the raw atomized metal powder (e.g., aluminum powder), the mass of each grinding ball when using a ball mill, the rotation speed of the grinding device, the degree of screening and filter press, etc. in the process of grinding the raw atomized metal powder (e.g., aluminum powder) using a ball mill, etc. and screening / filtering.
[0059] In addition, the metal particles do not necessarily need to be composed of only metals, and for example, particles of synthetic resins, particles of inorganic particles such as mica and glass whose surfaces are covered with metals, etc. may be used as long as the effects of the present invention are not impeded. In the present invention, particles composed of aluminum or aluminum alloys are preferred, especially from the viewpoints of high weather resistance, low specific gravity, and easy availability.
[0060] As the metal particles constituting the composite particles, aluminum flakes that are often used as metal pigments are particularly preferred. As aluminum flakes, aluminum flakes having surface properties, particle size, and shape required for metal pigments such as surface gloss, whiteness, and brightness are suitable. Aluminum flakes are usually commercially available in a paste state. Paste-like aluminum flakes can usually contain flaky aluminum powder, mineral spirits (aliphatic hydrocarbons) used during pulverization, residual components of fatty acids, and organic solvents such as solvent naphtha and xylene. Paste-like aluminum flakes can be used directly, or can be used by removing fatty acids on the surface in advance using organic solvents.
[0061] Alternatively, the composite particles may be used in a state where the volume average particle size (D 50 ) is a so-called aluminum vapor-deposited foil having a thickness of 3 μm to 30 μm inclusive and an average thickness of 20 nm to 300 nm inclusive.
[0062] 2. Preferred physical properties of the metallic pigment composition
[0063] The metallic pigment composition of the present invention is characterized by further satisfying the following physical property conditions.
[0064] (1) The composite particles are scaly in shape.
[0065] (2) Volume-based D when measuring the particle size distribution of composite particles using a laser diffraction particle size analyzer 50 is 3 μm or more and 30 μm or less,
[0066] (3) the average thickness of the composite particles is 20 nm or more and 300 nm or less,
[0067] (4) at least one of the covering layers is a silicon compound-containing layer,
[0068] (5) the ratio of the metal element content based on the metal particles in the composite particles to the silicon content based on the coating layer is 0.02 or more and 0.3 or less in terms of the ratio of the silicon content to the metal element content,
[0069] (6) The number ratio of the composite particles having a particle size of 0.1 μm or more and 1 μm or less is 10% or less relative to the total number of the composite particles in the metal pigment composition.
[0070] These physical property conditions are described below.
[0071] (1) The shape of the composite particles is scaly
[0072] The shape of the composite particles of the metal pigment composition of the present invention is flaky (thin flake). As a result, the coating formed using the metal pigment composition can exert high brightness, high angular color change, high hiding power, etc. In this specification, the shape of the composite particles is "flaky" (thin flake) means that the average diameter-to-thickness ratio (shape coefficient obtained by dividing the average particle diameter by the average thickness) of the composite particles is 10 or more. From the viewpoint of obtaining high brightness, angular color change, hiding power, etc., the average diameter-to-thickness ratio of the flaky composite particles is preferably 10 or more and 1500 or less. By having an average diameter-to-thickness ratio of 10 or more, a sufficient brightness can be exerted, and on the other hand, by having an average diameter-to-thickness ratio of 1500 or less, the mechanical strength of the flakes is maintained and a stable color tone can be obtained.
[0073] The "composite particles" in the physical property condition (1) refer to aggregates (aggregates) of a plurality of composite particles when the composite particles are aggregated or adhered.
[0074] Here, the average particle size used to calculate the average aspect ratio of the composite particles is a volume-based mean particle size called median diameter. 50 This will be described in detail in the description of condition (2) described later. In addition, the average thickness used to calculate the average aspect ratio of the composite particles will be described in detail in the description of condition (3) described later.
[0075] (2) Volume-based D when measuring the particle size distribution of composite particles using a laser diffraction particle size analyzer 50 3μ m or more and 30 μm or less
[0076] The volume-based D when the particle size distribution of composite particles is measured using a laser diffraction particle size analyzer 50 The volume-based D 50 Also often referred to as median particle size.
[0077] From the viewpoint of obtaining such high brightness, high angular color change, high hiding power, and small aggregation of each particle, the volume-based D when the particle size distribution of the composite particles is measured by a laser diffraction particle size analyzer is 50 The lower limit is 3 μm or more, and the upper limit is 30 μm or less, preferably 25 μm or less, and more preferably 20 μm or less.
[0078] The "composite particles" in the physical property requirement (2) refer to aggregates (aggregates) of a plurality of composite particles when the composite particles are aggregated or adhered.
[0079] Here, the volume-based D when the particle size distribution of the composite particles is measured using a laser diffraction particle size analyzer is:50 Refers to the particle size at which the cumulative volume of the cumulative particle size distribution is 50%. There is no particular limitation on the laser diffraction particle size distribution analyzer, and for example, "LA-300" (manufactured by Horiba, Ltd.) can be used. As the measurement solvent, isopropyl alcohol or mineral spirits can be used. For example, for a metal pigment composition containing composite particles of a sample, after 2 minutes of ultrasonic dispersion as a pretreatment, it is placed in a dispersion tank and after confirming that it is properly dispersed, D can be measured. 50 .
[0080] This method cannot measure the particle size of the composite particles in the resin composition described later. Therefore, as an alternative method in this case, for example, the following method can be used: the composite particles in the resin composition are photographed from the coating surface using an optical microscope, a laser microscope, etc., and the distribution of the equivalent circle diameter is obtained using commercially available image analysis software, thereby obtaining the particle size.
[0081] The volume-based D of the composite particles contained in the metal pigment composition 50 , can be controlled by appropriately adjusting the particle size of the raw material atomized metal powder, the mass of each grinding ball when using a ball mill, the rotation speed of the grinding device, the degree of screening and filter press, etc. in the process of grinding the raw material atomized metal powder (such as aluminum powder) using a ball mill and screening / filtering in the manufacturing method of the metallic pigment composition described later, and can be controlled by appropriately adjusting the type of organic silicon compound used in the process of covering the silicon-containing compound layer (and other covering layers as needed), the pH, concentration, stirring temperature, stirring time, type of stirring device, stirring power / degree (type and diameter of stirring wings, rotation speed, presence or absence of external stirring, etc.) in the covering process (when the organic silicon compound is hydrolyzed for use, this process is also included), etc.
[0082] (3) The average thickness of the composite particles is 20 nm or more and 300 nm or less
[0083] The average thickness of the composite particles having metal particles and a covering layer having one or more silicon-containing compound layers (i.e., silicon dioxide layers) on the surface contained in the metal pigment composition of the present invention is preferably 20 nm to 300 nm. Thus, in combination with satisfying the above conditions (1) to (2), the coating film formed using the metal pigment composition can exhibit further high brightness, high angle-dependent color, high hiding power, etc., while the aggregation of the composite particles constituting the metal pigment composition is suppressed and the aggregation property can be reduced.
[0084] Furthermore, when the conditions (4) to (6) described later are satisfied, the composition can exhibit high corrosion resistance even when used for water-based metallic paints, metallic coatings, etc., and can also exhibit excellent adhesion even when used for coatings such as metallic coatings.
[0085] From the above viewpoints, the average thickness of the composite particles is 20 nm or more as the lower limit and 300 nm or less, preferably 250 nm or less, and more preferably 200 nm or less as the upper limit.
[0086] The "composite particles" in the physical property condition (3) refer to aggregates (aggregates) of a plurality of composite particles when the composite particles are aggregated or adhered.
[0087] The average thickness of the composite particles can be calculated from the water surface diffusion area and density of the composite particles. The water surface diffusion area refers to the area occupied by a unit mass of dry composite particles when the dried composite particles are uniformly diffused on the water surface by the floating phenomenon and covered in a state without gaps. The water surface diffusion area can be measured according to the provisions of JIS K5906: 1998.
[0088] However, for the composite particles of the present invention, when the surface hydrophilicity is strong, it may be difficult to obtain the above-mentioned water surface diffusion area. In this case, the average thickness of the composite particles can be measured according to the method described in the examples described later. That is, a coating (thin film) is formed using a metal pigment composition in which the composite particles are dispersed in a mixture of an alcohol solvent such as methoxypropanol and water, and the thickness of the composite particles (500 or more) is observed using a scanning electron microscope (SEM), thereby obtaining the average thickness of the composite particles.
[0089] Average thickness and volume of composite particles contained in the metal pigment composition D 50 Similarly, in the process of grinding the raw material atomized metal powder (e.g., aluminum powder) using a ball mill and screening / filtering the raw material atomized metal powder (e.g., aluminum powder) using a ball mill, the particle size of the raw material atomized metal powder, the mass of each grinding ball when using a ball mill, the rotation speed of the grinding device, the degree of screening and filter press, etc. can be appropriately adjusted in the process of coating the silicon-containing compound layer (and other covering layers as needed), the pH, concentration, stirring temperature, stirring time, type of stirring device, stirring power / degree (e.g., type and diameter of stirring blades, rotation speed, presence or absence of external stirring), etc. in the coating process (when the organic silicon compound is hydrolyzed for use), the coating process can also be controlled.
[0090] (4) At least one of the covering layers is a silicon compound-containing layer
[0091] In the metal pigment composition of the present invention, at least one of the one or more covering layers formed on the surface of the metal particles serving as the core of the composite particles is a silicon compound-containing layer. This can suppress gas generation in the water-based paint, obtain good storage stability (i.e., corrosion resistance), and obtain excellent water resistance when forming a coating film.
[0092] Furthermore, when the aforementioned conditions (1) to (3) and the following conditions (5) to (6) are satisfied, even when used in a water-based metallic paint to form a metallic coating film, the coating film can exhibit excellent color tone due to high brightness, high angle-dependent color, and high hiding power, and can also exhibit excellent adhesion even when used in a coating film such as a metallic coating film.
[0093] The coating layer of the composite particles may have another coating layer (second coating layer) in addition to the silicon compound-containing layer. This second coating layer will be described further below.
[0094] The silicon compound-containing layer is preferably a layer composed of a compound containing a Si-O-bond (siloxane bond). Examples of such a layer include a layer containing at least one of a silane compound and a silicon oxide. Such a compound includes, in addition to the silane compound [H3SiO(H2SiO) n In addition to SiH3] (where n represents an arbitrary positive integer), silicon oxides represented by SiO2, SiO2·nH2O (where n represents an arbitrary positive integer) and the like can also be exemplified. These silane compounds and silicon oxides can be either crystalline or amorphous, but amorphous is particularly preferred. Therefore, as a layer containing silicon oxide (silicon dioxide, etc.), for example, a layer containing amorphous silicon dioxide can also be appropriately used.
[0095] In addition, the layer composed of the compound containing Si-O bonds can be a layer formed by using an organosilicon compound (containing a silane coupling agent) as a starting material. In this case, the silicon compound-containing layer can contain an organosilicon compound or a component derived therefrom within a range that does not hinder the effect of the present invention. In a typical example, the layer composed of the compound containing Si-O bonds can be formed by hydrolyzing an organosilicon compound.
[0096] The silicon compound-containing layer may contain additives, impurities, and the like other than the silicon compound within a range not impairing the characteristics of the present invention.
[0097] The silicon content in the silicon compound-containing layer is not particularly limited as long as it is an amount that satisfies the condition (5) described later.
[0098] The covering layer of the composite particles contained in the metal pigment composition of the present invention is particularly preferably hydrophilic. The composite particles usually form a metal pigment composition in the form of being dispersed in an aqueous solvent (water or a mixed solvent containing water and an organic solvent). When the covering layer has a hydrophilic surface, the composite particles can be highly dispersed in such an aqueous solvent. In addition, since silicon oxides (amorphous silicon dioxide, etc.) are very stable in aqueous solvents, a metal pigment composition containing highly stable composite particles in an aqueous solvent can be provided. From this point of view, for the composite particles contained in the metal pigment composition of the present invention, it is preferred that at least the outermost layer is a silicon compound layer (especially a layer composed of a compound containing an Si-O bond). In the case where the covering layer is composed of multiple layers, in addition to the outermost silicon compound layer, a silicon compound layer (especially a Si-O-based covering layer) can also be formed as a layer other than the outermost layer.
[0099] As described above, the thickness of the covering layer of each composite particle is not particularly limited as long as the average thickness of the composite particles is within the range of 20 nm or more and 300 nm or less, but is generally preferably within the range of about 5 to 50 nm (particularly 10 nm or more and 40 nm or less, and further 15 nm or more and 30 nm or less). When the thickness of the covering layer is 1 nm or more, a coating film having sufficient water resistance and in which corrosion or discoloration of metal particles in the water-based paint is suppressed can be obtained. On the other hand, when the thickness of the covering layer is about 50 nm or less, the brightness, distinctness of image, and concealment of the coating film can be maintained at a high level.
[0100] The thickness of the silicon compound layer contained in the covering layer of each composite particle is not particularly limited as described in the aforementioned condition (3) as long as the average thickness of the composite particles is in the range of not less than 20 nm and not more than 300 nm. However, from the perspective of the function of the layer, it can usually be in the range of not less than 5 nm and not more than 50 nm, and is particularly preferably in the range of not less than 10 nm and not more than 40 nm.
[0101] Specific examples of the organosilicon compound that can be used in the present invention will be further described below, but the organosilicon compound is not limited to these specific examples.
[0102] The organosilicon compound may contain at least one of the organosilicon compounds represented by the following general formula (1) and at least one selected from the group consisting of a silane coupling agent represented by any one of the following general formulas (2), (3) and (4), and partial condensates thereof.
[0103] Si(OR 1 )4(1)
[0104] (Where R 1is a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms, R 1 They may be all the same, partly the same, or all different.)
[0105] R 2 m Si(OR 3 ) 4-m (2)
[0106] (Where R 2 is a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms which may optionally contain a halogen group, R 3 is a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. 2 and R 3 Can be the same or different, R 2 or R 3 When there are two or more, they may all be the same, some may be the same, or all may be different. 1≤m≤3.)
[0107] R 4 p R 5 q Si(OR 6 ) 4-p-q (3)
[0108] (Where R 4 is a group containing a reactive group capable of chemically bonding with other functional groups, R 5 is a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms which may optionally contain a halogen group, R 6 is a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. 4 , R 5 , or R 6 When there are two or more, they may all be the same, some may be the same, or all may be different. 1≤p≤3, 0≤q≤2, 1≤p+q≤3. )
[0109] R 7 r SiCl 4-r (4)
[0110] (Where R 7 is a hydrogen atom or a hydrocarbon group having 1 to 30 carbon atoms which may optionally contain a halogen group, R 7 When there are two or more, they may all be the same, some may be the same, or all may be different. 0≤r≤3.)
[0111] As R in formula (1) 1Examples of hydrocarbon groups in the group include methyl, ethyl, propyl, butyl, hexyl, octyl, etc., which may be branched or linear. Among these hydrocarbon groups, methyl, ethyl, propyl, and butyl are particularly preferred. 1 They may be all the same, partly the same, or all different.
[0112] Preferred examples of the organosilicon compound of formula (1) include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, tetrabutoxysilane, etc. Among them, tetraethoxysilane is particularly preferred.
[0113] As R in formula (2) 2 Examples of hydrocarbon groups in include methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, dodecyl, oleyl, stearyl, cyclohexyl, phenyl, benzyl, naphthyl, etc. They may be branched or linear and may contain halogen groups such as fluorine, chlorine, and bromine. Among them, hydrocarbon groups having 1 to 18 carbon atoms are particularly preferred. 2 When there are two or more R, they may be all the same, partly the same, or all different. 2 In formula (2), the number of m=1 to 3, that is, 1 to 3, but m=1 or 2 is more preferable.
[0114] As R in formula (2) 3 Examples of hydrocarbon groups in R include methyl, ethyl, propyl, butyl, hexyl, octyl, etc., which may be branched or linear. Among these hydrocarbon groups, methyl, ethyl, propyl, and butyl are particularly preferred. 3 When there are two or more, they may be all the same, partially the same, or all different.
[0115] Preferred examples of the organosilicon compound (silane coupling agent) of formula (2) include methyltrimethoxysilane, methyltriethoxysilane, methyltributoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldibutoxysilane, trimethylmethoxysilane, trimethylethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-propyltributoxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltributoxysilane, dibutyldimethoxysilane, dibutyldiethoxysilane, dibutyldibutoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, dihexyldimethoxysilane, dihexyldiethoxysilane, octyltrimethoxysilane, Oxysilane, octyltriethoxysilane, dioctyldimethoxysilane, dioctyldiethoxysilane, dioctylethoxybutoxysilane, decyltrimethoxysilane, decyltriethoxysilane, didecyldimethoxysilane, didecyldiethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, di(octadecyl)dimethoxysilane, di(octadecyl)diethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, trifluoropropyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 3-chloropropyltributoxysilane, etc.
[0116] As R in formula (3) 4 Examples of the reactive group capable of chemically bonding with other functional groups include a vinyl group, an epoxy group, a styryl group, a methacryloxy group, an acryloxy group, an amino group, a ureide group, a mercapto group, a polysulfide group, and an isocyanate group.
[0117] In addition, R 4 When there are two or more R, they may be all the same, partly the same, or all different. 4 In formula (3), the number of is p=1 to 3, that is, 1 to 3, but p=1 is more preferable.
[0118] As R in formula (3) 5 Examples of hydrocarbon groups include methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, dodecyl, oleyl, stearyl, cyclohexyl, phenyl, benzyl, naphthyl, etc. They may be branched or linear and may contain halogen groups such as fluorine, chlorine, and bromine. Among them, hydrocarbon groups having 1 to 18 carbon atoms are particularly preferred. 5 When there are two or more, they may be all the same, partially the same, or all different.
[0119] As R in formula (3) 6 Examples of hydrocarbon groups in R include methyl, ethyl, propyl, butyl, hexyl, octyl, etc., which may be branched or linear. Among these hydrocarbon groups, methyl, ethyl, propyl, and butyl are particularly preferred. 6 When there are two or more, they may be all the same, partially the same, or all different.
[0120] Preferred examples of the organic silicon compound (silane coupling agent) of the formula (3) include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl-tri(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, p-phenylenediyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, N-2 -(Aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-ureidepropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyl-triethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, etc.
[0121] As R in formula (4) 7 Examples of hydrocarbon groups in include methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, dodecyl, oleyl, stearyl, cyclohexyl, phenyl, benzyl, naphthyl, etc. They may be branched or linear and may contain halogen groups such as fluorine, chlorine, and bromine. Among them, hydrocarbon groups having 1 to 12 carbon atoms are particularly preferred. 7 When there are two or more R, they may be all the same, partly the same, or all different. 7 In formula (4), the number of r=0-3, that is, 0-3, but r=1-3 is more preferable.
[0122] Preferred examples of the organosilicon compound (silane coupling agent) of the formula (4) include methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, octyldimethylchlorosilane, phenyltrichlorosilane, vinyltrichlorosilane, tetrachlorosilane and the like.
[0123] The organosilicon compound represented by the general formula (1) may be used alone or in combination of two or more thereof. In addition, the silane coupling agent represented by any one of the general formulas (2), (3) and (4) may be used alone or in combination of two or more thereof. When two or more thereof are used in combination, only two or more silane coupling agents represented by any one of (2), (3) and (4) may be used in combination, or two or more silane coupling agents represented by different general formulas may be used in combination.
[0124] The hydrolyzate of the organosilicon compound and / or its condensation reaction product is obtained by stirring and mixing the organosilicon compound, the amount of water required for the hydrolysis reaction, and the hydrolysis catalyst. In this case, a hydrophilic solvent may also be used as required. Various conditions for the hydrolysis reaction (i.e., the reaction for forming the silicon-containing compound layer) are described below.
[0125] As a raw material for the hydrolysis reaction and / or the condensation reaction for obtaining the hydrolyzate and / or the condensation reaction product of the organosilicon compound, an oligomer partially condensed in advance can be used.
[0126] The condensation reaction of the hydrolyzate of the organosilicon compound may be carried out simultaneously with the hydrolysis reaction of the organosilicon compound, or may be carried out in a separate step and with the catalyst replaced as necessary. In this case, heating may be performed as necessary.
[0127] The covering layer of the composite particles contained in the metal pigment composition of the present invention is not particularly limited except that at least one layer is a silicon compound-containing layer. If necessary, a covering layer other than the silicon compound-containing layer (hereinafter referred to as "second covering layer") may be formed.
[0128] The second covering layer may contain at least one of metals (alkali metals; alkaline earth metals; metals such as manganese, iron, cobalt, nickel, copper, and silver), metal oxides (titanium oxide, zirconium oxide, iron oxide, etc.), metal hydrates, and resins (acrylic resins, alkyd resins, polyester resins, polyurethane resins, polyvinyl acetate resins, nitrocellulose resins, fluororesins, and other synthetic resins). As the second covering layer, for example, a molybdenum-containing film or a phosphoric acid compound film may be formed. By providing the second covering layer, the corrosion resistance of the metal particles can be improved while promoting the formation of a silicon-containing compound layer.
[0129] The second covering layer (when formed) is particularly preferably formed between the metal particles and the silicon-containing compound layer. Therefore, for example, a layer structure of "metal particles / second covering layer / silicon-containing compound layer" can be appropriately adopted. Although not particularly limited, as examples of molybdenum-containing films, molybdenum-containing films disclosed in Japanese Patent Publication No. 2003-147226, International Publication No. 2004 / 096921 Pamphlet, Japanese Patent No. 5979788, and Japanese Patent Publication No. 2019-151678 can be cited. As an example of a phosphate compound film, a phosphate compound film disclosed in Japanese Patent No. 4633239 can be cited. As a preferred example of a molybdenum-containing substance constituting a molybdenum-containing film, a mixed coordination type heteropoly anion compound disclosed in Japanese Patent Publication No. 2019-151678 can be cited.
[0130] In other variations, the second covering layer can be formed outside the metal particles and the silicon-containing compound layer. In still other variations, the components of the second covering layer (molybdenum-containing compound, phosphate compound, etc.) can be included in the silicon-containing compound layer together with the silicon compound.
[0131] The mixed coordination type heteropolyanion compound used in the embodiment of forming the second covering layer (typically, the molybdenum-containing film) other than the silicon compound-containing layer of the composite particles contained in the metal pigment composition of the present invention is not particularly limited, and specific examples thereof include the following.
[0132] The mixed coordination type heteropoly anion of the mixed coordination type heteropoly anion compound that can be used has a structure in which some of the polyatoms of the heteropoly anion formed of one element are replaced by other elements, and exhibits physical properties different from those of a mixture of the heteropoly anions.
[0133] When using chemical formulas, if the mixed coordination heteropoly anion is represented by [X p M q N r O s ] t Then the heteropoly anion becomes [X p M q O s ] t , and furthermore with isopolyanions [M q O s ] t Here, X as a heteroatom represents an element of Group IIIB, IVB, or VB, such as B, Si, Ge, P, or As, and preferably B, Si, or P. M and N as polyatoms represent a transition metal, such as Ti, Zr, V, Nb, Ta, Mo, or W, and preferably Ti, Zr, V, Nb, Mo, or W.
[0134] In addition, p, q, r, and s represent atomic numbers, and t represents an oxidation number.
[0135] Since heteropolyanion compounds have many structures, mixed coordination type heteropolyanion compounds can have further structures. However, as representative and preferred mixed coordination type heteropolyanion compounds, the following mixed coordination type heteropoly acids can be exemplified: H3PW x Mo 12-x O 40 ·nH2O (phosphotungstomolybdic acid · n-hydrate), H 3+x PV x Mo 12-x O 40 ·nH2O (phosphovanadomolybdic acid n-hydrate), H4SiW x Mo 12-x O 40 ·nH2O (silicotungstomolybdic acid · n hydrate), H 4+x SiV x Mo 12-x O 40 ·nH2O (silicovanadomolybdic acid·n hydrate), etc. (where 1≤x≤11, n≥0)
[0136] Among these heteropoly anion compounds, H3PW3Mo9O 40 ·nH2O、H3PW6Mo6O 40 ·nH2O、H3PW9Mo3O 40 ·nH2O、H4PV1Mo 11 O 40 ·nH2O、H6PV3Mo9O 40 ·nH2O、H4SiW3Mo9O 40 ·nH2O, H4SiW6Mo6O 40 ·nH2O, H4SiW9Mo3O 40 ·nH2O、H5SiV1Mo 11 O 40 ·nH2O、H7SiV3Mo9O 40 nH2O and other mixed coordination heteropoly acids. (where n≥0)
[0137] The mixed coordination type heteropoly anion compound may be used in the form of an acid (so-called mixed coordination type heteropoly acid) or in the form of a (partial or complete) salt using a specific cation as a counter ion.
[0138] When the mixed coordination type heteropolyanion compound is used as a salt with a specific cation as a counter ion, the counter cation source can be selected from, for example, alkali metals such as lithium, sodium, potassium, rubidium, and cesium; alkaline earth metals such as magnesium, calcium, strontium, and barium; metals such as manganese, iron, cobalt, nickel, copper, zinc, silver, cadmium, lead, and aluminum; inorganic components such as ammonia; and at least one of amine compounds as organic components. Among the inorganic components, salts of alkali metals, alkaline earth metals, and ammonia are preferred.
[0139] Furthermore, when at least one selected from these alkali metals, alkaline earth metals, and ammonia is used as the counter cation source, it is more preferred to use a counter cation selected from H3PW x Mo 12-x O 40 ·nH2O (phosphotungstomolybdic acid · n-hydrate), H 3+x PV x Mo 12-x O 40 ·nH2O (phosphovanadomolybdic acid n-hydrate), H4SiW x Mo 12-x O 40 ·nH2O (silicotungstomolybdic acid · n hydrate), H 4+x SiV x Mo 12-x O 40 ·nH2O (silicovanadomobolic acid·n-hydrate) is used in the form of a salt of at least one of them.
[0140] Furthermore, it is also preferable to use an amine compound as an organic component as a counter cation source of the mixed coordination type heteropolyanion compound. As a specific example, an amine compound represented by the following general formula (5) is preferable.
[0141] (R 8 -N(-R 10 )-) n -R 9 (5)
[0142] (Where R 8 , R 9 and R 10 may be the same or different and may be a hydrogen atom or a monovalent or divalent hydrocarbon group having 1 to 30 carbon atoms and may contain any ether bond, ester bond, hydroxyl group, carbonyl group or mercapto group. 8 and R 9 together to form a 5-membered or 6-membered cycloalkyl group, or to form a 5-membered or 6-membered ring which may additionally contain nitrogen or oxygen atoms as a crosslinking group, or R 8 , R 9 and R 10 Together they form a polycyclic ring which may contain one or more additional nitrogen atoms and / or oxygen atoms as crosslinking groups.8 , R 9 and R 10 No hydrogen atom is formed simultaneously. n represents an integer from 1 to 2.)
[0143] As for the above-mentioned amine compound as the counter cation source of the mixed coordination type heteropolyanion compound, specifically, there can be exemplified straight-chain primary amines such as ethylamine, propylamine, butylamine, hexylamine, octylamine, laurylamine, tridecylamine, and stearylamine; branched primary amines such as isopropylamine, isobutylamine, 2-ethylhexylamine, and branched tridecylamine; straight-chain secondary amines such as dimethylamine, diethylamine, dipropylamine, dibutylamine, dihexylamine, dioctylamine, dilaurylamine, ditridecylamine, and distearylamine; branched secondary amines such as diisopropylamine, diisobutylamine, di-2-ethylhexylamine, and dibranched tridecylamine; N-methylbutylamine, N-ethylbutylamine, N-ethylhexylamine, N- Asymmetric secondary amines such as ethyl laurylamine, N-ethylstearylamine, N-isopropyloctylamine, and N-isobutyl-2-ethylhexylamine; straight-chain tertiary amines such as trimethylamine, triethylamine, tripropylamine, tributylamine, trioctylamine, trilaurylamine, tri(tridecyl)amine, and tristearylamine; branched-chain tertiary amines such as triisopropylamine, triisobutylamine, tri-2-ethylhexylamine, and tripronged tridecylamine; tertiary amines with mixed hydrocarbon groups such as N,N-dimethyloctylamine, N,N-dimethyllaurylamine, N,N-dimethylstearylamine, and N,N-diethyllaurylamine, and tertiary amines with mixed hydrocarbon groups such as allylamine, diallylamine, triallylamine, and N,N-dimethylallylamine alicyclic primary amines such as cyclohexylamine, 2-methylcyclohexylamine, etc.; primary amines with aromatic ring substituents such as aniline, benzylamine, 4-methylbenzylamine, etc.; alicyclic secondary amines such as N,N-dicyclohexylamine, N,N-di-2-methylcyclohexylamine, etc.; secondary amines with aromatic ring substituents such as dibenzylamine, N,N-di-4-methylbenzylamine, etc.; asymmetric secondary amines such as N-cyclohexyl-2-ethylhexylamine, N-cyclohexylbenzylamine, N-stearylbenzylamine, N-2-ethylhexylbenzylamine, etc.; alicyclic tertiary amines such as N,N-dimethylbenzylamine, N,N-dimethylcyclohexylamine, tricyclohexylamine, etc.; Tertiary amines with aromatic ring substituents; amines with ether bonds such as morpholine, 3-methoxypropylamine, 3-ethoxypropylamine, 3-butoxypropylamine, 3-decyloxypropylamine, and 3-lauryloxypropylamine; monoethanolamine, diethanolamine, monoisopropanolamine, monopropanolamine, butanolamine, triethanolamine, N,N-dimethylethanolamine, N-methylethanolamine, N-methyldiethanolamine, N-ethylethanolamine, N-propylethanolamine, N-isopropylethanolamine, N-butylethanolamine, N-cyclohexyl-N-methylaminoethanol, N-benzyl-N-propylaminoethanol, or alkanolamines such as N-hydroxyethylpyrrolidine, N-hydroxyethylpiperazine, and N-hydroxyethylmorpholine;Diamines such as ethylenediamine, N-methylethylenediamine, N,N'-dimethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, 1,2-propanediamine, 1,3-propanediamine, N,N-dimethyl-1,3-propanediamine, N-cyclohexyl-1,3-propanediamine, N-decyl-1,3-propanediamine, and N-isotridecyl-1,3-propanediamine; cyclic amines such as N,N'-dimethylpiperazine, N-methoxyphenylpiperazine, N-methylpiperidine, N-ethylpiperidine, quinuclidine, diazabicyclo[2,2,2]octane, and 1,8-diazabicyclo[5,4,0]-7-undecene; aromatic amines such as pyridine and quinoline, or any mixture thereof. ;
[0144] Among these amine compounds, preferred specific examples include at least one selected from primary amines, secondary amines, or tertiary amines, or alkanolamines having a straight-chain or branched alkyl group having 4 to 20 carbon atoms, such as butylamine, hexylamine, cyclohexylamine, octylamine, tridecylamine, stearylamine, dihexylamine, di-2-ethylhexylamine, straight-chain or branched ditridecylamine, distearylamine, tributylamine, trioctylamine, straight-chain or branched tritridecylamine, tristearylamine, N,N-dimethylethanolamine, N-methyldiethanolamine, triethanolamine, morpholine, and the like.
[0145] More preferably, at least one amine compound selected from the group consisting of H3PW x Mo 12-x O 40 ·nH2O (phosphotungstomolybdic acid · n-hydrate), H 3+x PV x Mo 12-x O 40 ·nH2O (phosphovanadomolybdic acid n-hydrate), H4SiW x Mo 12-x O 40 ·nH2O (silicotungstomolybdic acid · n hydrate), H 4+x SiV x Mo 12-x O 40 ·nH2O (silicovanadomobolic acid·n-hydrate) is used in the form of a salt of at least one of them.
[0146] Among the above-mentioned mixed coordination heteropoly anion compounds, H3PW is the most preferred x Mo 12-x O 40 ·nH2O (phosphotungstomolybdic acid · n-hydrate), H 3+x PV x Mo 12-x O 40 ·nH2O (phosphovanadomolybdic acid n-hydrate), H4SiW x Mo12-x O 40 Mixed coordination type heteropoly acids of nH2O (silicotungstomolybdic acid n-hydrate), or organic amine salts of these mixed coordination type heteropoly acids.
[0147] The second covering layer other than the silicon compound layer of the composite particles contained in the metal pigment composition of the present invention may be a layer containing other corrosion inhibitors in order to further improve the corrosion resistance of the metal particles (preferably aluminum particles or aluminum alloy particles) that serve as the core. There is no particular limitation on the corrosion inhibitor added, and any known corrosion inhibitor may be used. The amount used is sufficient as long as it does not hinder the desired effect of the present invention. Examples of such corrosion inhibitors include acidic phosphates, dimer acids, organic phosphorus compounds, metal salts of molybdic acid, and the like.
[0148] The silicon compound-containing layer of the composite particles contained in the metal pigment composition and / or the second covering layer, or as another layer, may further contain an organic oligomer or polymer from the viewpoint of adhesion and chemical resistance when forming a coating film.
[0149] In addition, the silicon compound-containing layer and / or the second covering layer of the composite particles, or as another layer, may contain at least one selected from the group consisting of inorganic phosphoric acids and their salts, and acidic organic (sub)phosphites and their salts from the viewpoint of storage stability.
[0150] These compounds are not particularly limited, and for example, compounds disclosed in JP-A-2019-151678 can be used.
[0151] (5) The content of the metal element in the composite particles based on the metal particles and the content of the silicon in the coating layer based on the metal element in the composite particles based on the metal element in the coating layer The content ratio is 0.02 or more and 0.3 or less as a ratio of the silicon content to the metal element content.
[0152] The composite particles contained in the metal pigment composition of the present invention have metal particles serving as their cores and one or more covering layers on the surface of the metal particles. Furthermore, as described in detail in the above description of condition (4), at least one layer of the covering layer is a silicon-containing compound layer (so-called silicon dioxide layer). Therefore, the composite particles of the metal pigment composition of the present invention have as constituent components the metal element constituting the metal particles serving as the cores of the composite particles and the silicon element derived from the silicon-containing compound layer (so-called silicon dioxide layer) constituting the covering layer on the surface of the metal particles.
[0153] In the composite particles contained in the metal pigment composition of the present invention, the ratio of the silicon content to the metal element content is preferably 0.02 or more and 0.3 or less. Here, the content of each element in the composite particles can be determined by, for example, dissolving the metal pigment composition and analyzing the content of the metal element and the content of the silicon element in the composite particles contained therein by high-frequency inductively coupled plasma (ICP) emission spectrometry.
[0154] The content of metal elements in the metal particles constituting the core of the composite particles is proportional to the size of the metal particles (i.e., particle size), and the content of silicon elements originating from the silicon-containing compound layer (so-called silicon dioxide layer) constituting the covering layer on the surface of the metal particles is proportional to the thickness of the silicon-containing compound layer (so-called silicon dioxide layer).
[0155] When the above ratio is 0.02 or more, the thickness of the silicon-containing compound layer (so-called silicon dioxide layer) in the covering layer on the surface of the metal particles relative to the particle size of the metal particles becomes a thickness that can effectively exert corrosion resistance. In addition, when the above ratio is 0.3 or less, the above thickness becomes a thickness that can effectively exert the optical properties of the metal particles. For the above ratio, as a lower limit, it is 0.02 or more, preferably 0.03 or more, and more preferably 0.04 or more. As an upper limit, it is 0.3 or less, preferably 0.2 or less, and more preferably 0.15 or less. That is, the composite particles of the metal pigment composition of the present invention can effectively exert both the corrosion resistance based on the silicon-containing compound layer (so-called silicon dioxide layer) in the covering layer of the composite particles and the optical properties based on the characteristics of the metal particles that become the core of the composite particles (for example, excellent coating film color tone achieved by high brightness, high angle-shifting color, and high hiding) by the ratio of the above metal element content to the above silicon element content. Specifically, by effectively exerting the corrosion resistance based on the silica layer, even when used as water-based paints such as water-based metallic paints, water-based inks, etc., gas generation is suppressed to obtain good storage stability, and the water resistance when used as a coating film is also excellent. In addition, by effectively exerting the optical properties based on the original characteristics of the metal particles, even when used in water-based metallic paints, metal coatings, etc., an excellent coating film color tone achieved by high brightness, high angle-shifting color, and high hiding power is obtained.
[0156] Furthermore, by satisfying the aforementioned conditions (1) to (4) and the condition (6) described below, the coating film can further exhibit excellent coating color tone such as high hiding power and brightness, and can also exhibit excellent adhesion even when used for coating films such as metal coating films.
[0157] The "composite particles" in the physical property condition (5) refer to aggregates (aggregates) of a plurality of composite particles when the composite particles are aggregated or adhered.
[0158] As described above, metal particles may be used alone or in combination of two or more metals formed from only one metal element (i.e., metals formed from two or more metal elements). For example, when the metal particles that serve as the core of the composite particles are composed of a metal formed from one metal element, the " Metal elements constituting the aforementioned metal particles " refers to the one metal element. For example, when the metal particles that become the core of the composite particles are composed of metals formed by two metal elements, the " Metal constituting the aforementioned metal particles element " refers to the two metal elements. That is, if the metal particle that becomes the core of the composite particle is an aluminum metal particle formed only by the aluminum element, then the " Metal elements constituting the aforementioned metal particles ” refers to aluminum metal element, and if the metal particles serving as the cores of the composite particles are metal particles formed of two metal elements, namely, aluminum element and other metal element, it refers to the aluminum metal element and the other metal element.
[0159] As described above, the metal particles in the present invention are preferably aluminum or an aluminum alloy, more preferably aluminum. The amount of the metal particles contained in the composite particles and the silicon content contained in the silicon-containing compound layer constituting the covering layer on the surface of the metal particles are not particularly limited as long as they are amounts that can satisfy the above ratio (i.e., the present condition (5)).
[0160] (6) The number ratio of the composite particles having a particle size of 0.1 μm or more and 1 μm or less relative to the composite particles The total amount of particles in the above-mentioned metal pigment composition is less than 10%
[0161] The number ratio of composite particles having a particle size of 0.1 μm or more and 1 μm or less (hereinafter also referred to as fine composite particles) in the total number of composite particles (ie, the total number) contained in the metallic pigment composition of the present invention is 10% or less.
[0162] As described in the aforementioned condition (4), excellent corrosion resistance can be obtained by forming at least one layer of the covering layer formed on the surface of the metal particle that becomes the core of the composite particle contained in the metal pigment composition of the present invention as a silicon compound layer (so-called silicon dioxide layer). In addition, in order to obtain excellent corrosion resistance, the silicon dioxide layer has a certain thickness that satisfies the aforementioned condition (5). However, in tiny composite particles with a particle size of 1 μm or less (specifically, except for composite particles with a particle size of less than 0.1 μm, which are not recognized as composite particles because their size is too small and their influence on the performance of the present invention can be ignored, it refers to composite particles with a particle size of 0.1 μm or more and 1 μm or less (i.e., tiny composite particles)), the ratio of the thickness of the silicon dioxide layer to the particle size of the metal particle that becomes the core of the composite particle increases, and the ratio of the metal itself in the composite particle decreases. Therefore, if the number ratio of the fine composite particles in the metal pigment composition increases, the original optical properties of the metal particles (such as excellent coating color tone achieved by high brightness, high angle-dependent color, and high hiding power) cannot be exerted. In addition, since the thickness of such fine composite particles is relatively thick relative to the particle size, it is difficult to orient the fine composite particles, and the orientation of the entire metal pigment is hindered, and the original optical properties of the metal particles cannot be exerted.
[0163] Furthermore, fine composite particles having a particle size of 1 μm or less inhibit the adhesion between the substrate and the coating. Therefore, if a large number of fine composite particles are present in the metallic pigment composition and the composition is used as a coating, the adhesion of the coating resin to the substrate is likely to decrease.
[0164] In the metal pigment composition of the present invention, the number ratio of the fine composite particles to the total number of composite particles in the metal pigment composition is 10% or less. As a result, the number of composite particles having a fine particle size in all composite particles contained in the metal pigment composition is suppressed, so that the original optical properties of the metal particles (such as high brightness, high angle-shifting color, and high hiding power) can be exerted.
[0165] Furthermore, in combination with satisfying the aforementioned conditions (1) to (5), the excellent coating color tone achieved by high brightness, high angle-shifting color, and high hiding power is further exerted, and at the same time, the aggregation of the composite particles constituting the metal pigment composition is suppressed, thereby effectively exerting the corrosion resistance based on the silica layer. As a result, even when used as a water-based paint such as a water-based metallic paint, a water-based ink, etc., gas generation can be suppressed, good storage stability is obtained, and excellent water resistance when used as a coating film.
[0166] The number ratio of the fine composite particles is 10% or less, preferably 5% or less, more preferably 3% or less, relative to the total number of composite particles in the metallic pigment composition, and is preferably as low as possible from the above viewpoint.
[0167] The "composite particles" in the physical property requirement (6) refer to aggregates (aggregates) of a plurality of composite particles when the composite particles are aggregated or adhered.
[0168] There is no particular limitation on the method for determining the number ratio of composite particles (i.e., micro composite particles) having a particle size of 0.1 μm or more and 1 μm or less. For example, it can be determined as follows: a coating film is prepared using the metal pigment composition of the present invention, and the coating film is photographed using a digital microscope (e.g., KH-3000 manufactured by HiROX Corporation) at a magnification such that the total number of particles (i.e., the total number of all composite particles) is approximately 500 or more. Image analysis software (e.g., Image-ProPLUS ver.7.0 manufactured by MediaCybernetics Corporation) is used to extract particles with an equivalent circle diameter of 0.1 μm or more and 1 μm or less from all the particles contained therein, and the particles are measured as the number relative to the total number of particles, thereby determining the number ratio of the micro composite particles. Here, the equivalent circle diameter refers to the diameter of a circle having the same area as the projected area of the particle image, and is generally referred to as the Heywood diameter. For example, even if there are particles that are not circular and have a deformed shape, if their area is, for example, 78.5 nm 2 If the particle size is equal to the area of a circle with a particle size of 10 nm, the particle size is also regarded as 10 nm. In addition, when the particles are aggregated / adhesive to each other and the boundary cannot be visually confirmed, the equivalent circle diameter can be calculated from the cross-sectional area of the deformed shape in the aggregated / adhesive state. Even if a certain degree of aggregation / adhesion occurs, when the boundary can be visually confirmed at this magnification, the particle size (equivalent circle diameter) of each particle can be measured.
[0169] It should be noted that, as mentioned above, with respect to the "composite particles" in the physical property condition (6), extremely small composite particles having a particle size of less than 0.1 μm (specifically, composite particles having an equivalent circle diameter of less than 0.1 μm) are not considered composite particles because their size is too small to affect the performance of the present invention in a negligible manner.
[0170] In addition, the volume distribution of the composite particles is measured by a laser diffraction particle size analyzer. 50 The number ratio of the composite particles having a particle size three times or more of the above (hereinafter also referred to as coarse composite particles) is preferably 3% or less relative to the number of all composite particles in the metal pigment composition (ie, the total number).
[0171] Thereby, when a coating film is formed, a dense metal coating film can be formed, and roughness of the surface when the coating film is formed can be suppressed.
[0172] Furthermore, in combination with satisfying the aforementioned conditions (1) to (6), while further exhibiting excellent coating film color tone such as high hiding power and brightness, aggregation of the composite particles constituting the metal pigment composition is suppressed. Furthermore, even when used as a water-based paint such as a water-based metallic paint, a water-based ink, etc., gas generation can be suppressed, and good storage stability can be obtained. When used as a coating film, it has excellent water resistance, and even when used in a coating film such as a metal coating film, it can exhibit excellent adhesion.
[0173] The number ratio of the coarse composite particles is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less, relative to the total number of composite particles in the metallic pigment composition.
[0174] The "composite particles" in the present physical property conditions refer to aggregates (aggregates) thereof when a plurality of composite particles are aggregated / adhesive.
[0175] The method for measuring the coarse composite particles is not particularly limited, and for example, the method of observing the coating film with a digital microscope, similar to the method of measuring the fine composite particles, or a laser diffraction particle size distribution analyzer may be used.
[0176] The number ratio of the fine composite particles to the coarse composite particles contained in the metal pigment composition of the present invention can be controlled mainly by appropriately selecting the particle size of the metal particles used and, in the step of coating the silicon-containing compound layer (and other covering layers as required), appropriately adjusting the stirring time, the type of stirring device, the power / degree of stirring (the type and diameter of the stirring blade, the rotation speed, the presence or absence of external stirring, etc.). In particular, the number ratio of the fine composite particles contained in the metal pigment composition of the present invention is preferably controlled by removing the metal particles with a fine particle size (grinding and classification under mild conditions) before the step of coating the silicon-containing compound layer (and other covering layers as required) and stirring under mild conditions in the step of coating the silicon-containing compound layer (and other covering layers as required), as described later.
[0177] 3. Method for producing metallic pigment composition
[0178] The metal pigment composition of the present invention can be suitably produced, for example, by the following production method, which includes the steps of producing predetermined flaky (thin-flaky) metal particles from a slurry of metal powder through grinding, washing, sieving (classification), filtering, concentrating, etc., and then covering the metal particles with a silicon-containing compound layer under stirring using a solvent containing water and / or a hydrophilic solvent. More specifically, the following methods can be cited, but are not limited thereto.
[0179] The metal pigment composition of the present invention can be suitably produced, for example, by the following method, which includes a step of forming a silicon-containing compound layer on the surface of the metal particles by subjecting the organosilicon compound to a hydrolysis / (partial) condensation reaction in a mixed solution containing (a) metal particles, (b) a silicon-containing raw material containing at least one of the organosilicon compounds, (c) a solvent (water and / or a hydrophilic solvent), and other optional components as required (silicon-containing compound layer forming step). This step can usually be carried out under stirring.
[0180] (1) Crushing, screening (grading), and filtering processes
[0181] Here, the case where aluminum particles are used as metal particles will be described as an example.
[0182] Aluminum particles are usually ground by atomized aluminum powder and / or aluminum foil using a method commonly used in the pigment industry such as a dry ball mill method, a wet ball mill method, a grinder method, or a stamping mill method in the presence of a grinding aid and an inactive solvent to form so-called flaky (thin-flaky) aluminum particles. After this process, aluminum particles with large particle sizes are removed by screening (classification), and a paste-like aluminum particle pigment is obtained through necessary processes such as filtering, washing, and mixing. In this specification, it is also referred to as "paste-like aluminum flake pigment".
[0183] Here, the flaky (thin-flaky) aluminum particles having a large particle size refer to aluminum particles that cannot pass through a #300 to #800 metal mesh.
[0184] In the present invention, when the atomized aluminum powder and / or aluminum foil is ground, it is preferably carried out under mild conditions. This is because, by doing so, the generation of composite particles with a particle size of 1 μm or less (specifically, composite particles with a particle size of less than 0.1 μm are not identified as composite particles because their size is too small and their influence on the performance of the present invention can be ignored, so they refer to composite particles with a particle size of 0.1 μm or more and 1 μm or less) can be effectively suppressed.
[0185] Here, the mild conditions refer to the conditions of reducing the mass of each grinding ball, reducing the rotation speed of the grinding device, etc. by appropriately adjusting and combining them.
[0186] In addition to the above operations, it is also considered to reduce the average particle size (D 50 ) is adjusted to within the range of this embodiment and to ensure good productivity, so as to determine the grinding conditions.
[0187] Considering the average particle size (D 50 ) is in the range of 3 μm to 30 μm, the particularly preferred grinding conditions are: as the raw material, atomized aluminum powder with a particle size of 1 to 30 μm is preferably used, the mass of each grinding ball used in the grinding device is preferably set to 0.08 to 11 mg, and the rotation speed of the grinding device is 33% to 78% relative to the critical speed (Nc), more preferably 36% to 57%.
[0188] From the viewpoint of easily reducing the ratio of fine particles and from the viewpoint of improving the surface smoothness of the aluminum particles, the specific gravity of grinding balls used in a ball mill or the like is preferably 8 or less, more preferably 7.5 or less, and further preferably 7 or less.
[0189] It should be noted that the specific gravity of the grinding balls is preferably greater than that of the grinding solvent. The grinding balls are prevented from floating in the solvent, and sufficient shear stress between the grinding balls is obtained, which tends to ensure sufficient grinding.
[0190] As grinding balls used in the method for producing aluminum pigments of this embodiment, grinding balls with high surface smoothness, such as steel balls, stainless steel balls, zirconia balls, and glass balls, are preferred from the viewpoint of adjusting the surface smoothness of aluminum particles and the durability of the grinding balls.
[0191] On the other hand, steel balls, alumina balls, and the like having low surface smoothness are not preferred from the viewpoint of adjusting the surface smoothness of the aluminum particles and the durability of the grinding balls.
[0192] Therefore, for example, in the case of a steel ball, it is preferable to use a steel ball whose surface smoothness has been improved by mechanical polishing or chemical polishing.
[0193] As described above, the mass of one grinding ball is preferably 0.08 to 11 mg.
[0194] By using grinding balls with a mass of 0.08 mg or more, the grinding balls do not move individually but move in groups or masses, thereby reducing the shear stress between the grinding balls and preventing grinding, which is called group motion.
[0195] In addition, by using grinding balls with a mass of 11 mg or less, excessive impact force can be prevented from being applied to the aluminum powder, thereby preventing the occurrence of warping, deformation, cracks, etc.
[0196] As the atomized aluminum powder used as a raw material, one containing less impurities other than aluminum is preferred.
[0197] The purity of the atomized aluminum powder is preferably 99% or more, more preferably 99.5% or more, and further preferably 99.7% or more.
[0198] The average particle size of the atomized aluminum powder used as a raw material is preferably 2 to 25 μm.
[0199] The shape of the atomized aluminum powder used as the raw material is preferably a spherical powder, a teardrop-shaped powder, etc. By using these, there is a tendency that the shape of the aluminum pigment is not easily distorted when ground. On the other hand, needle-shaped powder and amorphous powder are not preferred because the shape of the aluminum pigment is easily distorted when ground.
[0200] When the aluminum pigment of the present embodiment is produced by a grinding device including a ball mill, it is preferred to use a grinding solvent.
[0201] The type of grinding solvent is not limited to the following, and examples thereof include conventionally used hydrocarbon solvents such as mineral spirits and solvent naphtha, and low-viscosity solvents such as alcohols, ethers, ketones, and esters.
[0202] As grinding conditions for the atomized aluminum powder, the volume of the grinding solvent is preferably 1.5 to 16.0 times, more preferably 2.0 to 12.0 times, relative to the mass of aluminum in the atomized aluminum powder. When the volume of the grinding solvent is 1.5 times or more relative to the mass of aluminum in the atomized aluminum powder, warping, deformation, cracking, etc. associated with long-term grinding of the atomized aluminum powder can be prevented, so it is preferred.
[0203] In addition, by setting the volume of the grinding solvent to be 16.0 times or less relative to the mass of aluminum in the atomized aluminum powder, uniformity in the mill during grinding is improved, the atomized aluminum powder is effectively in contact with the grinding media, and there is a tendency for appropriate grinding to be performed.
[0204] The volume of the grinding balls is preferably 0.5 to 3.5 times, more preferably 0.8 to 2.5 times, the volume of the grinding solvent (volume of the grinding balls / volume of the grinding solvent).
[0205] When the volume of the grinding balls is 0.5 times or more relative to the volume of the grinding solvent, the uniformity of the grinding balls in the mill during grinding is improved, and grinding tends to be performed appropriately.
[0206] In addition, by making the volume of the grinding balls less than 3.5 times the volume of the grinding solvent, the ratio of the grinding balls in the mill is formed in an appropriate range, and the ball stacking will not be too high, thereby preventing the problems of shape degradation such as warping, deformation, cracking, etc. of the particles due to grinding stress, and preventing the brightness from decreasing and the scattered light from increasing, which is preferred.
[0207] When the aluminum pigment of the present embodiment is produced by a grinding device equipped with a ball mill, it is preferred to use a grinding aid in addition to the above-mentioned grinding solvent.
[0208] Examples of pulverization aids include fatty acids, aliphatic amines, aliphatic amides, aliphatic alcohols, and the like. Oleic acid, stearic acid, stearylamine, and the like are generally preferred. In addition, examples of inactive solvents include hydrophobic inactive solvents such as mineral spirits, solvent naphtha, LAWS, HAWS, toluene, and xylene, which can be used alone or in combination. The pulverization aids and inactive solvents are not limited to these.
[0209] The grinding aid is preferably used in an amount of 0.2 to 30% by mass based on the mass of the atomized aluminum powder.
[0210] The grinding balls used for grinding the atomized aluminum powder preferably have a diameter of 0.6 to 2.4 mm.
[0211] By using grinding balls having a diameter of 0.6 mm or more, the stacking of grinding balls does not become too low, and the pressure applied to the aluminum particles during grinding is within an appropriate range, so that grinding tends to be performed appropriately.
[0212] In addition, by using grinding balls with a diameter of 2.4 mm or less, the stacking of grinding balls will not be too high, and the problem of shape degradation such as warping, deformation, cracking, etc. of particles caused by the weight of the balls can be prevented, and the reduction in brightness and the increase in scattered light can be prevented, which is preferred.
[0213] As described above, the rotation speed of the ball mill during the pulverization of the atomized aluminum powder is preferably 33% to 78% of the critical rotation speed (Nc).
[0214] When the ratio of the rotation speed to the critical rotation speed is 33% or more, the uniformity of the movement of the aluminum slurry and the balls in the ball mill is maintained, which is preferable.
[0215] In addition, by setting the ratio of rotation speed to critical speed to be below 78%, the grinding balls are prevented from being stirred up or falling due to their own weight, the impact force exerted on the aluminum particles by the grinding balls will not be too high, and the problems of shape degradation such as warping, deformation, cracking, etc. of the particles are prevented, so it is preferred.
[0216] It should be noted that the aluminum pigment of the present embodiment can be produced by a vacuum deposition method other than the above-mentioned production method including the step of grinding the atomized aluminum powder.
[0217] As the pulverization step, pulverization by a wet ball mill method is preferred from the viewpoint of preventing dust explosion and ensuring safety.
[0218] In addition, in the present invention, it is preferred to remove the aluminum particles with a small particle size in advance by classification before forming a covering layer containing at least one silicon-containing compound layer on the surface of the flaky (thin-flaky) aluminum particles. This is because, by doing so, the generation of composite particles with a particle size of less than 1 μm (specifically, except for composite particles with a particle size of less than 0.1 μm, which are not identified as composite particles because their size is too small to ignore the effect on the performance of the present invention, and therefore refer to composite particles with a particle size of 0.1 μm or more and 1 μm or less) in the composite particles obtained by forming a covering layer containing at least one silicon-containing compound layer on the surface of the aluminum particles can be effectively suppressed. Specifically, the ratio of the number of composite particles with a particle size of 0.1 μm or more and 1 μm or less in the aluminum pigment can be suppressed to less than 10% relative to the total number of composite particles in the aluminum pigment. This classification is used in combination with the above-mentioned grinding under mild conditions. The generation suppression of small composite particles can be further improved.
[0219] However, the above-mentioned grinding process under mild conditions and the classification for removing the above-mentioned flaky (thin-flaky) aluminum particles with a fine particle size do not necessarily need to be two processes, and only one of them may be performed as needed. That is, the above-mentioned grinding process under mild conditions may not be performed, and only the process of removing the flaky (thin-flaky) aluminum particles with a fine particle size by classification after the usual grinding process may be performed, or only the above-mentioned grinding process under mild conditions may be performed without performing the subsequent classification process.
[0220] As a classification process for removing flaky (thin-flaky) aluminum particles with a fine particle size, wet classification is preferred from the viewpoint of ensuring safety, and there are methods using machines such as gravity classifiers (sedimentation classifiers), pyramid classifiers, hydraulic classifiers, siphon classifiers, centrifugal classifiers, hydrocyclones, jet classifiers, rake classifiers, Atkins classifiers, spiral classifiers, classification tanks, hydraulic separators, and sedimentation centrifuges.
[0221] As the metal particles used in the manufacture of the metal pigment composition of the present invention, a so-called vapor-deposited aluminum pigment produced by peeling a metal layer vapor-deposited on a support material such as a resin film by physical vapor deposition (PVD) from the support material and pulverizing the metal layer may be used. In this case, it is also important to appropriately adjust the pulverization conditions to suppress the generation of fine particles or to remove fine particles by classification.
[0222] (2) Silicon compound-containing layer formation step
[0223] The mixed solution containing the above-mentioned (a) metal particles, (b) silicon-containing raw material containing at least one organic silicon compound, and (c) solvent, and other optional components as required, can be produced by mixing these components. The order of mixing is not particularly limited.
[0224] As the metal particles (a) mentioned above, particles of aluminum or aluminum alloy can be particularly preferably used. Also, as for the particle shape, scaly (thin-flaky) metal particles can be preferably used as described above.
[0225] The content (solid content) of the metal particles in the mixed solution is not particularly limited as long as the metal pigment composition of the present invention is obtained, and can be appropriately set depending on the type and particle size of the metal particles used.
[0226] As the silicon-containing raw material, an organosilicon compound is used. The organosilicon compound is not limited, but the above-mentioned organosilicon compounds can be preferably used.
[0227] At least one of the organosilicon compound represented by the above formula (1) (as a typical example, tetraalkoxysilane) and / or its condensate, and the silane coupling agent represented by any one of the above formulas (2) to (4) can be suitably used.
[0228] Hereinafter, the case where tetraalkoxysilane is used as the organosilicon compound represented by the above formula (1) will be described as an example. In addition, tetraalkoxysilane and / or its condensate may be collectively referred to as "tetraalkoxysilane" in some cases.
[0229] When the tetraalkoxysilane represented by the above formula (1) and the silane coupling agent represented by any one of the above formulas (2) to (4) are used in combination, a method of mixing the two can be used (referred to as "the first method"). Alternatively, a method including the steps of treating the metal particles with one to form a first silicon-containing compound layer and treating the metal particles with the other to form a second silicon-containing compound layer can be used (referred to as "the second method").
[0230] As the first method, for example, there can be cited a method comprising the step of forming a silicon compound-containing layer by appropriately adjusting the pH of a mixed solution containing metal particles, a tetraalkoxysilane represented by the above formula (1), and a silane coupling agent represented by any one of the above formulas (2) to (4), thereby causing a hydrolysis / condensation reaction between the tetraalkoxysilane and the silane coupling agent.
[0231] As the second method, for example, there can be listed a method comprising: a step of appropriately adjusting the pH of a mixed solution containing metal particles and a tetraalkoxysilane represented by the above formula (1) to allow the tetraalkoxysilane to undergo a hydrolysis / condensation reaction, thereby forming a first silicon-containing compound layer (for example, a silicon dioxide film formed of amorphous silicon dioxide) on the surface of the metal particles; and a step of appropriately adjusting the pH of a mixed solution containing metal particles and a silane coupling agent represented by any one of the above formulas (2) to (4) to allow the silane coupling agent to undergo a hydrolysis / condensation reaction, thereby forming a second silicon-containing compound layer on the surface of the first silicon-containing compound layer.
[0232] The amount of the tetraalkoxysilane or its condensate represented by the above formula (1) can be appropriately set according to the type of tetraalkoxysilane used, etc. For example, from the viewpoint of the coating treatment effect, and from the viewpoint of suppressing the aggregation of metal particles or the reduction of the glossiness, etc., the amount is preferably 2 parts by mass or more and 200 parts by mass or less, more preferably 3 parts by mass or more and 100 parts by mass or less, and further preferably 5 parts by mass or more and 60 parts by mass or less, relative to 100 parts by mass of the metal particles (solid content).
[0233] The amount of the silane coupling agent represented by any of the above formulae (2) to (4) is not particularly limited, but is preferably 0.1 parts by mass or more and 20 parts by mass or less, more preferably 0.5 parts by mass or more and 15 parts by mass or less, and further preferably 1 part by mass or more and 10 parts by mass or less, based on 100 parts by mass of the metal particles (solid content), from the viewpoint of the desired coating treatment effect, etc.
[0234] As the solvent in the mixed solution, that is, the solvent used for the hydrolysis reaction and / or condensation reaction of the organosilicon compound, it can be appropriately selected according to the type of silicon-containing raw material used, and water, a hydrophilic organic solvent, or a mixed solvent thereof can usually be used. These solvents can improve the uniformity of the reaction and the uniformity of the obtained hydrolyzate and / or condensation reaction product. In the method of directly forming the silicon-containing compound layer on the metal particles, from the viewpoint of avoiding the rapid reaction between the metal particles and water, it is particularly preferred that the solvent of the mixed solution contains a hydrophilic organic solvent. In the present invention, a mixed solvent of water and a hydrophilic organic solvent can be appropriately used.
[0235] The hydrophilic organic solvent is not particularly limited, and examples thereof include alcohols such as methanol, ethanol, propanol, butanol, isopropanol, and octanol; ether alcohols such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monoethyl ether, propylene glycol monomethyl ether, and dipropylene glycol monomethyl ether, and their esters; diols such as ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, polyoxyethylene glycol, polyoxypropylene glycol, and ethylene propylene glycol; ethyl cellosolve, butyl cellosolve, acetone, methoxypropanol, ethoxypropanol, and other alkoxy alcohols, etc. These can be used alone or in combination.
[0236] When a mixed solvent of water and a hydrophilic organic solvent is used as the solvent, the ratio between the two is not particularly limited as long as the metallic pigment composition of the present invention is obtained.
[0237] The amount of solvent used in the step of forming the silicon-containing compound layer (except for the amount of solvent used for the prior dispersion of metal particles) is not limited, and is usually about 100 to 10,000 parts by mass relative to 100 parts by mass of metal particles (solid content), and is particularly preferably 200 parts by mass or more and 1,000 parts by mass or less. By using a solvent amount of more than 100 parts by mass, the increase in viscosity of the mixed solution (slurry) is suppressed, and proper stirring can be performed. In addition, by using a solvent amount of less than 10,000 parts by mass, the recovery and regeneration costs of the treatment liquid can be prevented from increasing. It should be noted that the amount of solvent used here, in the case of the above-mentioned second method, refers to the total amount of solvent used for the formation of the first silicon-containing compound layer and the formation of the second silicon-containing compound layer.
[0238] The mixed solution may contain other additives as needed within the range that does not hinder the effect of the present invention, for example, surfactants, metal corrosion inhibitors, etc. in addition to catalysts such as hydrolysis catalysts and dehydration condensation catalysts.
[0239] Among them, a hydrolysis catalyst can be preferably used. By adding a hydrolysis catalyst, the organosilicon compound can be effectively hydrolyzed and dehydrated and condensed while adjusting the pH of the mixed solution, and as a result, a silicon-containing compound layer can be effectively and reliably formed on the surface of the metal particles.
[0240] The hydrolysis catalyst can be any known or commercially available one without particular limitation. As the hydrolysis catalyst, for example, inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, organic acids such as benzoic acid, acetic acid, chloroacetic acid, salicylic acid, oxalic acid, picric acid, phthalic acid, malonic acid, etc. can be used; phosphonic acids such as vinylphosphonic acid, 2-carboxyethanephosphonic acid, 2-aminoethanephosphonic acid, octanephosphonic acid, etc. can be used. These hydrolysis catalysts can be used alone or in combination of two or more.
[0241] In addition, as the hydrolysis catalyst, for example, inorganic bases such as ammonia, sodium hydroxide, potassium hydroxide, etc.; inorganic base salts such as ammonium carbonate, ammonium bicarbonate, sodium carbonate, sodium bicarbonate, etc.; amines such as monomethylamine, dimethylamine, trimethylamine, monoethylamine, diethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, N,N-dimethylethanolamine, ethylenediamine, pyridine, aniline, choline, tetramethylammonium hydroxide, guanidine, etc.; and salts of organic acids such as ammonium formate, ammonium acetate, monomethylammonium formate, dimethylammonium acetate, pyridine lactate, guanidinoacetic acid, acetic aniline, etc. These hydrolysis catalysts may be used alone or in combination.
[0242] The amount of the hydrolysis catalyst added is not particularly limited, and is generally 0.01 to 20 parts by mass relative to 100 parts by mass of the metal particles (solid content), and is particularly preferably 0.02 to 10 parts by mass. By adding 0.01 parts by mass or more, the amount of precipitation of the silicon-containing compound layer can be sufficient. In addition, by adding 20 parts by mass or less, the aggregation of the metal particles can be effectively suppressed.
[0243] When the mixed solution is produced, the components may be mixed so as to be uniformly distributed in the mixed solution, and the order of mixing is not particularly limited.
[0244] In the production of the metallic pigment composition of the present invention, it is preferred that the production of the mixed solution is carried out under stirring at an appropriate intensity.
[0245] The temperature of the mixed solution may be either room temperature or heated. Generally, the temperature of the mixed solution is 20°C or higher and 90°C or lower, and is preferably controlled within the range of 30°C or higher and 80°C or lower. When the temperature is 20°C or higher, the formation rate of the silicon-containing compound layer increases, and the treatment time can be shortened. On the other hand, when the temperature is 90°C or lower, the reaction is easily controlled, and the probability of obtaining the desired composite particles can be increased.
[0246] As the agitator for stirring the mixed solution, it is not particularly limited, and a known agitator that can effectively and evenly stir the mixed solution containing aluminum particles and the organosilicon compound can be used. As a specific example, a kneader, a mixing machine, a rotary container agitator, a stirring reaction tank, a V-type agitator, a double cone agitator, a spiral mixer, a toggle agitator, a rapid mixer, an air flow agitator, a ball mill, a wheel mill, etc. can be listed. A further description of the agitator is described below.
[0247] The temperature of the mixed solution containing metal particles and the organosilicon compound when stirring is generally about 10 to 100° C., and is particularly preferably 30° C. or higher and 80° C. or lower. When the temperature is 10° C. or higher, the reaction time for obtaining a sufficient treatment effect can be shortened. In addition, when the temperature is 100° C. or lower, the control of the reaction for obtaining a desired metal pigment composition becomes easier.
[0248] The stirring time of the mixed solution is not particularly limited as long as it is a sufficient time for forming the desired silicon-containing compound layer. The stirring time is preferably, for example, 0.5 hours or more and 10 hours or less, more preferably 1 to 5 hours. By stirring for more than 0.5 hours, a sufficient treatment effect can be obtained. In addition, by stirring for less than 10 hours, the increase in treatment cost can be suppressed.
[0249] In the mixed solution, the silicon-containing raw material undergoes a hydrolysis / condensation reaction to form a silicon-containing compound layer on the surface of the metal particles (or via the second covering layer). The hydrolysis / condensation reaction can be performed by adjusting the pH of the mixed solution.
[0250] When adjusting the pH, especially in the stage where the silicon-containing compound layer is formed on the surface of the metal particles (or through the second covering layer), the pH of the mixed solution changes, so it is preferably appropriately adjusted so that the pH can be maintained within a constant range. At this time, it is preferred to adjust the pH by adding a hydrolysis catalyst, but other acidic or basic compounds may be used to adjust the pH as long as the characteristics of the metal pigment composition of the present invention are not impaired.
[0251] When an alkaline hydrolysis catalyst is used as the hydrolysis catalyst, the pH value is preferably 7 or more and 11 or less, and more preferably 7.5 or more and 10 or less. When the pH value is 7 or more, the silicon compound-containing layer can be formed rapidly. On the other hand, when the pH value is 11 or less, the aggregation of metal particles and the reduction of brilliance can be suppressed, and the generation of hydrogen gas due to corrosion can be prevented.
[0252] When an acidic hydrolysis catalyst is used as the hydrolysis catalyst, the pH is preferably 1.5 or more and 4 or less, and more preferably 2 or more and 3 or less. When the pH is 1.5 or more, the reaction is appropriately controlled, and a metal pigment composition containing desired composite particles is easily obtained. On the other hand, when the pH is 4 or less, the precipitation rate of the silicon-containing compound layer can be kept high.
[0253] In the case of adopting any of the above-mentioned first method and second method, it is preferred that the hydrolyzate and / or condensate of the organosilicon compound represented by the above-mentioned general formula (1) is added in an amount of 0.01 to 50 parts by mass, more preferably 1 to 30 parts by mass, based on the state in which the hydrolysis and condensation reactions are completed, relative to 100 parts by mass of the metal particles (solid content). In addition, the hydrolyzate and / or condensate derived from the silane coupling agent represented by any of the above-mentioned general formulas (2) to (4) and / or their partial condensates is added in an amount of 0.01 to 0.8 parts by mass, more preferably 0.01 to 0.7 parts by mass, relative to 100 parts by mass of the metal particles (solid content), based on the state in which the hydrolysis and condensation reactions are completed.
[0254] The amount of the hydrolyzate and / or condensate of the organosilicon compound represented by the general formula (1) can be calculated by multiplying the mass of the organosilicon compound represented by the general formula (1) used in the preparation of the metallic pigment composition by the mass ratio before and after the reaction when the organosilicon compound is completely hydrolyzed and condensed.
[0255] For example, when tetraethoxysilane (TEOS) is used as the organosilicon compound represented by the general formula (1), the amount of the hydrolyzate and / or its condensate to be added can be calculated using the following mass ratio before and after the hydrolysis and condensation reaction.
[0256] (hydrolysis)
[0257] Si(OC2H5)4(molecular weight: 208)+4H2O→Si(OH)4(molecular weight: 96)+(C2H5OH)4
[0258] (condensation)
[0259] Si(OH)4(molecular weight: 96)+Si(OH)4(molecular weight: 96)→(SiO2)2(molecular weight: 60×2)+4H2O
[0260] The mass before and after the above hydrolysis and condensation reaction is 60 / 208=0.288 times. Therefore, for example, when 10 parts by mass of TEOS is used relative to 100 parts by mass of metal particles (solid content), the added amount of its hydrolyzate and / or its condensate is 0.288 times that, that is, 2.88 parts by mass.
[0261] Similarly, the amount of the hydrolyzate and / or condensate thereof of the silane coupling agent represented by any one of the general formulae (2) to (4) can be calculated by multiplying the mass of the silane coupling agent represented by any one of the general formulae (2) to (4) and / or its partial condensate used in the production of the metallic pigment composition by the mass ratio before and after the reaction when the silane coupling agent and / or its partial condensate is completely hydrolyzed and condensed.
[0262] For example, when methyltrimethoxysilane is used as the silane coupling agent represented by the general formula (2), the amount of the hydrolyzate and / or its condensate to be added of the silane coupling agent can be calculated using the following mass ratio before and after the hydrolysis and condensation reaction.
[0263] (hydrolysis)
[0264] CH3Si(OCH3)3(molecular weight: 136)+3H2O→CH3Si(OH)3(molecular weight: 94)+(CH3OH)3
[0265] (condensation)
[0266] CH3Si(OH)3(molecular weight: 94)+CH3Si(OH)3(molecular weight: 94)→(SiCH3O 1.5 )2(molecular weight: 67×2)+3H2O
[0267] The mass before and after the above hydrolysis / condensation reaction is 67 / 136=0.49 times, so for example, when 1.23 mass parts of methyltrimethoxysilane is used relative to 100 mass parts of metal particles (solid content), the added amount of its hydrolyzate and / or its condensate is 0.49 times that, that is, 0.60 mass part.
[0268] In addition, in the case of adopting any of the above-mentioned first method and second method, it is preferred that the metal particles are fully dispersed in water, a hydrophilic organic solvent, or a mixed solvent thereof before being combined with an organic silicon compound as a silicon compound source (or before being combined with a molybdenum compound in the case of forming a second covering layer). In such preliminary dispersion (initial dispersion), it is preferred to temporarily extract a portion of the dispersion liquid (for example, 0.5 mass % or more and 30 mass % or less, preferably 1 mass % or more and 20 mass % or less, and more preferably 1 mass % or more and 15 mass % or less of the total dispersion liquid) to the outside of the dispersion tank and then return it to the dispersion tank for external circulation, thereby further improving the degree of dispersion. The dispersibility can be further improved by performing ultrasonic treatment outside the dispersion tank in the middle of the flow path of the external circulation.
[0269] Ultrasonic treatment is not particularly limited, and can be carried out with usually more than 10W and less than 1000W, preferably more than 50W and less than 800W, usually more than 20 seconds and less than 10 minutes, preferably about 30 seconds to 5 minutes. In addition, from the viewpoint of obtaining sufficient dispersion by appropriately adjusting the intensity of stirring, the amount of the solvent used for such pre-dispersion can usually be about 100 to 10000 mass parts, preferably more than 200 mass parts and less than 5000 mass parts, more preferably more than 300 mass parts and less than 1000 mass parts relative to 100 mass parts of metal particles (solid content).
[0270] Such preliminary dispersion of metal particles can be performed generally at 10° C. to 80° C., preferably 15° C. to 60° C., and most preferably at room temperature (about 20 to 30° C.). In addition, the preliminary dispersion of metal particles (including ultrasonic treatment when performed) can be performed for 5 minutes to 10 hours, preferably 10 minutes to 5 hours.
[0271] (3) Second Covering Layer Formation Step
[0272] As described above, the second covering layer (if formed) is particularly preferably formed between the metal particles and the silicon-containing compound layer. Therefore, a layer structure of "metal particles / second covering layer / silicon-containing compound layer" can be preferably adopted.
[0273] There is no particular limitation on the second covering layer, and it may be a molybdenum-containing film, a phosphate compound film, etc. As a preferred example of a molybdenum-containing substance constituting the molybdenum-containing film, a mixed coordination type heteropoly anion compound disclosed in Japanese Patent Publication No. 2019-151678 can be cited. For examples of the constituent components of the second covering layer including the mixed coordination type heteropoly anion compound, as described above.
[0274] Hereinafter, a method in which a molybdenum-containing coating is formed between the metal particles and the silicon-containing compound layer as the second coating layer will be described as an example.
[0275] In the case of forming a molybdenum-containing coating as the second covering layer between the metal particles and the silicon-containing compound layer, the molybdenum-containing coating can be formed on the surface of the metal particles by stirring a mixed solution containing metal particles and a molybdenum compound (typically a mixed coordination heteropolyanion compound) before forming the silicon-containing compound layer.
[0276] The method for forming a molybdenum-containing film on the surface of the metal particles is not particularly limited, as long as it is a method that can uniformly stir a mixed solution containing metal particles and a molybdenum compound in an aqueous solvent. For example, by stirring or kneading a mixed solution containing metal particles and a molybdenum compound in a slurry state or a paste state, a molybdenum-containing film can be formed on the surface of the metal particles. In the mixed solution, the molybdenum compound can be dissolved or dispersed.
[0277] In addition, the agitator for stirring the mixed solution containing the metal particles and the molybdenum compound is not particularly limited, and a known agitator that can effectively and uniformly stir the mixed solution containing the aluminum particles and the molybdenum compound can be used. As specific examples, a kneader, a mixing machine, a rotary container agitator, a stirring reaction tank, a V-type agitator, a double cone agitator, a spiral mixer, a zigzag agitator, a rapid mixer, an air flow agitator, a ball mill, a wheel mill, etc. can be listed. The examples of the stirring wing of the agitator are not particularly limited, and anchor wings, paddles, propeller blades, turbine blades, etc. can be listed.
[0278] The amount of the molybdenum compound can be appropriately set according to the type of molybdenum compound used. The amount is usually 0.02 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the metal particles (solid content), and is particularly preferably 0.1 parts by mass or more and 10 parts by mass or less. When the above content is 0.02 parts by mass or more, a sufficient treatment effect can be obtained. In addition, when the above content is 20 parts by mass or less, the brilliance of the obtained metal pigment composition can be kept high.
[0279] As a solvent used for mixing the metal particles and the molybdenum compound, water, a hydrophilic organic solvent, or a mixed solvent thereof can be generally used.
[0280] Examples of the hydrophilic organic solvent include alcohols such as methanol, ethanol, propanol, butanol, isopropanol, and octanol; ether alcohols such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monoethyl ether, propylene glycol monomethyl ether, and dipropylene glycol monomethyl ether, and their esters; diols such as ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, polyoxyethylene glycol, polyoxypropylene glycol, and ethylene propylene glycol; ethyl cellosolve, butyl cellosolve, acetone, methoxypropanol, ethoxypropanol, and other alkoxy alcohols, etc. These can be used alone or in combination.
[0281] The amount of solvent used in the step of forming the second covering layer (in the case of pre-dispersing the metal particles, except for the amount of solvent used therefor) is not particularly limited, and is usually 50 parts by mass or more and 5000 parts by mass or less, more preferably 100 parts by mass or more and 2000 parts by mass or less, relative to 100 parts by mass of the metal particles (solid content). When the amount of solvent used is 50 parts by mass or more, the partial distribution of the molybdenum compound and the aggregation of the metal particles can be suppressed. In addition, when the amount of solvent used is 5000 parts by mass or less, a sufficient treatment effect for the metal particles using the molybdenum compound can be obtained.
[0282] The temperature of the mixed solution containing the metal particles and the molybdenum compound when stirring is generally about 10 to 100° C., and is particularly preferably 30° C. or higher and 80° C. or lower. When the temperature is 10° C. or higher, the reaction time for obtaining a sufficient treatment effect can be shortened. In addition, when the temperature is 100° C. or lower, the control of the reaction for obtaining a desired metal pigment composition becomes easier.
[0283] The stirring time of the mixed solution is not particularly limited as long as it is sufficient time for forming the desired molybdenum-containing film. The stirring time is, for example, preferably more than 0.5 hours and less than 10 hours, more preferably more than 1 hour and less than 5 hours. By stirring for more than 0.5 hours, a sufficient treatment effect can be obtained. In addition, by stirring for less than 10 hours, the increase in processing cost can be suppressed.
[0284] After the stirring of the mixed solution containing metal particles and molybdenum compounds is completed, the particles formed with the second covering layer can be recovered. At this time, known washing, solid-liquid separation, etc. can be appropriately implemented as needed. For example, it is preferred to use a hydrophilic organic solvent to wash the mixed solution, and then filter it using a filter, so that water and unreacted products are removed from the filter cake containing metal particles having a molybdenum-containing film. In this way, a molybdenum-containing film as the second covering layer can be formed. In the case of forming other second covering layers, it can also be implemented according to the above method.
[0285] In the method of forming a second covering layer (molybdenum-containing film) on metal particles and then forming a silicon-containing compound layer, after the stirring of the mixed solution containing metal particles and the molybdenum compound is completed, the particles formed with the second covering layer may be directly added / stirred to the system with a dispersion of a silicon compound source (typically, an organic silicon compound represented by the above formula (1), such as tetraalkoxysilane and / or its condensate, and at least one of the silane coupling agents represented by any one of the above formulas (2) to (4)) in water and / or a hydrophilic organic solvent. In this case, a dispersion of an organic silicon compound represented by the above formula (1), such as tetraalkoxysilane and / or its condensate, may be added to the system containing the particles formed with the second covering layer, and then a dispersion of at least one of the silane coupling agents represented by any one of the above formulas (2) to (4) may be added / stirred (refer to the second method in the above-mentioned "step of forming a silicon-containing compound layer").
[0286] (4) Stirring conditions
[0287] In the manufacture of the metal pigment composition of the present invention, at least the step of forming the silicon-containing compound layer needs to be carried out under stirring. In addition, in the manufacture of the metal pigment composition of the present invention, it is preferred that not only the step of forming the silicon-containing compound layer but also the step of forming the second covering layer be carried out under stirring. In the above-mentioned method of pre-dispersing the metal particles, it is more preferred that it is also carried out under stirring. In addition, in the manufacture of the metal pigment composition of the present invention, it is further preferred that all the steps including the pre-dispersion of the metal particles, the step of forming the second covering layer, and the step of forming the silicon-containing compound layer be carried out under stirring.
[0288] In the production of the metal pigment composition of the present invention, by performing at least the step of forming the silicon-containing compound layer under appropriately controlled stirring, it is possible to effectively suppress or prevent the composite particles from being attached to each other via the silicon-containing compound layer or the phenomenon that the aggregated particles including the metal particles are covered by the silicon-containing compound layer. In addition, by performing all the steps including the prior dispersion of the metal particles, the step of forming the second covering layer, and the step of forming the silicon-containing compound layer (until the formation of all the layers to be formed on the surface of the metal particles is completed) under stirring, it is possible to more easily obtain the metal pigment composition of the present invention that satisfies all of the physical property conditions (1) to (6) above.
[0289] The following description of stirring conditions can be applied to any step in the production of the metallic pigment composition of the present invention.
[0290] The stirring can be carried out using a known or commercially available stirring device. For example, at least one of a kneader, a mixer, a rotary container stirrer, a stirring reaction tank, a V-type stirrer, a double cone stirrer, a spiral mixer, a zigzag stirrer, a rapid mixer, an air flow stirrer, a ball mill, a wheel mill, etc. can be used.
[0291] The stirring is particularly preferably carried out under mild conditions.
[0292] Here, the mild conditions refer to stirring at a low speed of 0.5 m / sec to 20 m / sec at the tip of the stirring blade when the silicon compound-containing layer forming step is performed in a stirring reaction tank.
[0293] This is because, by performing such stirring at a low speed, the generation of composite particles with a micro-size (specifically, composite particles with a particle size of less than 0.1 μm are not considered as composite particles because their size is too small to have a negligible effect on the performance of the present invention, and therefore refer to composite particles with a particle size of 0.1 μm or more and 1 μm or less) in the composite particles obtained by forming a covering layer including at least one silicon compound layer on the surface of the metal particles can be effectively suppressed. Specifically, the number ratio of composite particles with a particle size of 0.1 μm or more and 1 μm or less in the metal pigment composition can be suppressed to 10% or less relative to the total number of composite particles in the metal pigment composition. The stirring under mild conditions can be used in combination with the above-mentioned grinding and classification under mild conditions to more effectively reduce the ratio of composite particles with a micro-size.
[0294] Among the above-mentioned stirrers, a stirring tank type device using stirring blades for stirring is preferably used. The stirring blades exert a circulation effect to make the entire reaction system including the liquid phase flow while exerting a pressure shearing effect, resulting in more effective suppression of the formation of aggregated composite particles.
[0295] The shape of the stirring wing is not particularly limited, for example, anchor type, propeller shape, turbine shape, inclined turbine shape, fan turbine shape, blade shape, inclined blade shape, door shape can be used. MAXBLEND wing (Sumitomo Heavy IndustriesProcess Equipment Co., Ltd. system), FULLZONE wing (Kobelco Eco-Solutions Co., Ltd. system) etc. are also suitable. In addition, the stirring wing of these shapes can also be combined in multiple stages.
[0296] The stirring speed is preferably such that the stirring blades are not exposed due to the vortex generated by the stirring. In order to suppress the vortex generated by the stirring, a cylindrical tank, a square tank, or a tank provided with a baffle plate can be used appropriately.
[0297] In the manufacture of the metal pigment composition containing composite particles of the present invention, it is preferred to set the most suitable stirring tank, the size of the stirring wing, and the speed of the stirring wing by the relationship with the amount and physical properties (density, viscosity, etc.) of the mixed solution. The size of the stirring tank is preferably selected in such a way that the maximum amount of the mixed solution used in a series of processes is more than 20% and less than 80% of the stirring tank. In the case of a cylindrical stirring tank, the ratio of the height (L) to the inner diameter (D) of the stirring tank, L / D, is usually in the range of more than 0.5 and less than 3.0, and is usually in the range of more than 1 and less than 2. In addition, for the size of the stirring wing, it is usually appropriate that the maximum diameter is in the range of more than 0.2 and less than 0.9 of the inner diameter of the stirring tank, and is set to a degree of more than 0.4 and less than 0.6. The shape (including length) of the stirring wing is preferably appropriately selected according to the physical properties of the mixed solution, and it is important that the stirring tank is stirred as a whole in all processes. Particularly preferably, a tilted blade type, a tilted turbine type, a propeller type multi-stage combination that is easy to produce up and down flow in a manner that no unstirred stop portion appears near the bottom surface of the liquid surface or the stirred tank, or a MAXBLEND wing or a FULLZONE wing is used. At this time, the distance between the stirring wing and the inner surface of the stirred tank (including the baffle) is preferably separated by more than 5mm. By doing so, it is easy to suppress the damage and deformation of the metal particles.
[0298] The speed of the stirring blade is preferably 0.5 m / s to 20 m / s at the front end, more preferably 1 m / s to 15 m / s, and further preferably 2 m / s to 10 m / s. When the speed of the stirring blade tip is within the range of 0.5 m / s to 20 m / s, the dispersibility of the composite particles in the generated metal pigment composition can be improved, and thus it is easy to obtain a metal pigment composition with low aggregation of each particle, excellent hiding power, color tone, and less gas generation. In addition, when the linear speed of stirring is within the above range, the damage of the metal particles (such as flaky aluminum powder) is prevented, the speed of the hydrolysis / condensation reaction is appropriately controlled, and the aggregation of the composite particles can be effectively suppressed.
[0299] (5) Composite particle recovery process
[0300] After the process of forming the silicon-containing compound layer (and the optional second covering layer) of the metal particles is completed, the obtained composite particles can be recovered. During recovery, known treatments such as washing and solid-liquid separation can also be implemented as needed. For example, it is preferred to use an organic solvent to wash the dispersion, filter it with a filter, and remove water and unreacted products from the filter cake containing the composite particles. In addition, the filter cake containing the composite particles can be heat-treated at a temperature in the range of 100 to 500° C. as needed. The composite particles recovered in this way can usually constitute a small amount of solvent residue containing water / hydrophilic solvent used in the manufacturing process, and a metal pigment composition formed by association, as described later.
[0301] 4. Metallic pigment composition
[0302] The metallic pigment composition of the present invention obtained as described above is understood to be a metallic pigment composition which forms composite particles including metal particles and one or more covering layers on the surface thereof, and further contains a solvent such as water / hydrophilic solvent used in the production process as a residual portion of the solid content (non-volatile content).
[0303] In the metallic pigment composition, the silicon compound which is a hydrolyzate and / or a condensate thereof of an organic silicon compound (e.g., at least one of the organic silicon compounds represented by the general formula (1) above, and at least one of the silane coupling agents represented by any one of the general formulas (2), (3) and (4) above, and their partial condensates) can be present in an amount of 0.02 to 50 parts by mass based on the state in which the hydrolysis / condensation reaction is completed, relative to 100 parts by mass of the metal particles.
[0304] In the metallic pigment composition, the compound forming the arbitrarily selected second covering layer (for the arbitrarily selected embodiment of forming a molybdenum-containing film as the second covering layer, a molybdenum-containing compound such as a mixed coordination heteropolyanion compound) can be present in an amount of 0.01 to 10 parts by mass based on 100 parts by mass of the metal particles.
[0305] In the metal pigment composition, the arbitrarily selected organic oligomer or polymer may be present in an amount of 0.01 to 50 parts by mass based on 100 parts by mass of the metal particles.
[0306] In the metal pigment composition, at least one selected from the group consisting of arbitrarily selected inorganic phosphoric acids and salts thereof, and acid organic (phosphite) esters and salts thereof may be present in an amount of 0.01 to 20 parts by mass based on 100 parts by mass of the metal particles.
[0307] In the metal pigment composition, as a residual part of the above-mentioned components (non-volatile components), a solvent containing water / hydrophilic solvent used in the production process may exist. The amount of the solvent containing water / hydrophilic solvent may be, for example, 0.5% by mass or more and 95% by mass or less of the metal pigment composition. Alternatively, the amount of the solvent containing water / hydrophilic solvent may be 1% by mass or more and 90% by mass or less, or 2% by mass or more and 80% by mass or less, or 5% by mass or more and 70% by mass or less of the metal pigment composition.
[0308] The metal pigment composition may contain any optional components other than those described above. Examples of the optional components include at least one of an antioxidant, a light stabilizer, a polymerization inhibitor, and a surfactant.
[0309] As the antioxidant, antioxidants represented by phenolic compounds, phosphorus compounds, and sulfur compounds can be used.
[0310] As the light stabilizer, the light stabilizer used as the above-mentioned antioxidant can also be used, and light stabilizers represented by benzotriazole compounds, benzophenone compounds, salicylate compounds, cyanoacrylate compounds, oxalic acid derivatives, hindered amine compounds (HALS), and hindered phenol compounds can be used.
[0311] 5. Use of the Metal Pigment Composition
[0312] This metal pigment composition can be used for water-based coatings, inks, etc. In addition, this metal pigment composition can be added to a water-based coating or water-based ink formed by dissolving or dispersing a resin as a coating film forming component (binder) in a medium mainly composed of water to form a metallic water-based coating or a metallic water-based ink. In addition, the metal pigment composition can also be mixed with a resin and used as a water-resistant binder or filler. Antioxidants, light stabilizers, and surfactants can be added when the metal pigment composition is mixed with a water-based coating or a water-based ink, or a resin, etc.
[0313] When the metal pigment composition is used for coatings and inks, it can be directly added to (water-based) coatings or (water-based) inks, but it is preferably dispersed in a solvent before adding. As the solvent used, water, dodecyl alcohol ester, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, etc. can be listed. In addition, as these resins, for example, acrylic resins, polyester resins, polyether resins, epoxy resins, fluororesins, rosin resins, etc. can be listed. In addition, as an example of a binder for coatings or inks, in addition to resins, rubber can also be listed.
[0314] These resins are preferably emulsified, dispersed or dissolved in water. To this end, the carboxyl groups, sulfonic acid groups and the like contained in the resins may be neutralized.
[0315] Preferred resins are acrylic resins and polyester resins.
[0316] As required, resins such as melamine-based curing agents, isocyanate-based curing agents, and urethane dispersions can be used in combination. Furthermore, it can be combined with coloring pigments such as inorganic pigments, organic pigments, and body pigments that are usually added to the coating, silane coupling agents, titanium coupling agents, dispersants, sedimentation prevention agents, leveling agents, thickeners, and defoamers. In order to make the dispersion of the coating good, a surfactant can be further added. In order to make the storage stability of the coating good, an antioxidant, a light stabilizer, and an inhibitor can be further added.
[0317] Examples of the coloring pigment include phthalocyanine, quinacridone, isoindolinone, perylene, azo lake, iron oxide, chrome yellow, carbon black, titanium oxide, pearl mica, and the like.
[0318] The content of the metal pigment composition of the present invention in the above-mentioned water-based paint or water-based ink (resin composition) is not limited, and is usually 0.1% by mass or more and 50% by mass or less, and is particularly preferably 1% by mass or more and 30% by mass or less. When the content is 0.1% by mass or more, a high decorative (metal) effect can be obtained. In addition, when the content is 50% by mass or less, the characteristics of the water-based paint or water-based ink, such as weather resistance, corrosion resistance, mechanical strength, etc., can be prevented from being damaged.
[0319] The content of the solvent is not particularly limited, and may be 20% to 200% by mass relative to the binder content. When the content of the solvent is within this range, the viscosity of the coating or ink is adjusted to an appropriate range, and handling and film formation can be facilitated.
[0320] The coating method or printing method of water-based paint etc. is not particularly limited. For example, various coating methods or printing methods can be appropriately adopted in consideration of the form of water-based paint etc., the surface shape of the coated material etc. As the coating method, for example, a spray method, a roller coater method, a brush coating method, a scraper coating method etc. can be listed. In addition, as the printing method, for example, gravure printing, screen printing etc. can be listed.
[0321] The coating film formed by water-based paint etc. can be formed on the primer or mid-coat layer formed by electrodeposition coating etc. In addition, a top coat layer etc. can be formed on the coating film formed by water-based paint etc. as needed.
[0322] In the case of these layer structures, each coating layer may be applied, and the next coating layer may be applied after curing or drying, or each coating layer may be applied by so-called wet-on-wet coating, and the next coating layer may be applied without curing or drying. From the viewpoint of obtaining a coating film having good mirror-like brilliance, the aqueous coating material containing the metallic pigment composition of the present invention preferably adopts a method including a step of applying a base coating layer, curing or drying it, and then forming a coating layer using an aqueous coating material.
[0323] The coating composition in each coating layer may be cured by heat curing or room temperature curing. In addition, the coating composition in each coating layer may be dried by, for example, hot air or natural drying at room temperature.
[0324] The thickness of the coating layer formed by water-based paint or the like is not particularly limited, but is generally preferably 0.5 μm or more and 100 μm or less. When the thickness of the coating layer is 0.5 μm or more, the concealing effect of the base achieved by the ink or paint can be fully obtained. In addition, when the thickness of the coating layer is 100 μm or less, drying becomes easy, and the occurrence of defects such as wrinkles and sagging can be suppressed.
[0325] Example
[0326] The present invention is described in more detail below by way of examples. However, it should be noted that these examples are merely illustrative and the present invention is not limited in any way by the description of these examples.
[0327] 1. Evaluation methods of various physical properties used in Examples and Comparative Examples
[0328] The evaluation methods of various physical properties used in Examples and Comparative Examples are as follows.
[0329] (1) Average particle size D 50 Determination of
[0330] The aluminum pigment compositions obtained in the examples and comparative examples were used as samples, and the volume-based D of the composite particles contained therein was 50 The measurement was performed using a laser diffraction particle size distribution meter "LA-300" (manufactured by Horiba, Ltd.).
[0331] Mineral spirits were used as a measurement solvent.
[0332] The sample metal pigment composition containing composite particles was subjected to ultrasonic dispersion for 2 minutes as a pretreatment and then placed in a dispersion tank. After confirming that the composition had an appropriate concentration, D was measured. 50 .
[0333] (2) Determination of the ratio of Si element to Al element
[0334] The contents of aluminum element and silicon element in the composite particles contained in the aluminum pigment composition obtained in each of the Examples and Comparative Examples were measured by high-frequency inductively coupled plasma (ICP) emission spectrometry.
[0335] (3) Determination of composite particle number ratio
[0336] The number of composite particles (micro composite particles) having a particle size of 0.1 μm or more and 1 μm or less in the aluminum pigment composition obtained in each example and comparative example and the volume-based D of the composite particles obtained by the above measurement are shown in FIG. 50 The number of composite particles having a particle size three times or more of the particle size of the metal (coarse composite particles) is measured by preparing a metallic coating to form a coating film and measuring the number of composite particles contained in the coating film.
[0337] First, a metallic paint having the following composition is prepared.
[0338] Aluminum pigment composition: 0.25 g as non-volatile component
[0339] Isopropyl alcohol: 18.0 g
[0340] Acrylic resin (※1): 24g
[0341] Melamine resin (※2): 5g
[0342] ※1: Made by DIC Co., Ltd., ACRYDIC 47712
[0343] ※2: Made by DIC Co., Ltd., AMIDIR J-820-60
[0344] The aluminum pigment composition used was the aluminum pigment composition obtained in each of Examples and Comparative Examples.
[0345] To prepare a test piece for observation, the metal coating prepared using the above formulation was first applied to a polyethylene terephthalate film (PET film) using a 1 mil applicator, left to stand at room temperature for 20 minutes, and then sintered at 140° C. for 20 minutes to prepare a coated plate.
[0346] Next, the coating film of the prepared coated plate was photographed at a magnification of 700 times using a microscope (manufactured by HiROX: KH-3000), and using image analysis software (manufactured by Media Cybernetics: Image-ProPLUS ver.7.0), particles with an equivalent circle diameter of 0.1 μm or more and 1 μm or less, and particles with an equivalent circle diameter exceeding D 100 based on the volume of composite particles measured using the above-mentioned laser diffraction particle size distribution meter "LA-300" (manufactured by Horiba, Ltd.) were extracted. 50 The former is used as the number ratio (%) of the composite particles having a particle size of 0.1 μm or more and 1 μm or less, and the latter is used as the volume basis D when the volume distribution of the composite particles is measured using a laser diffraction particle size analyzer. 50 The number ratio (%) of composite particles having a particle size that is 3 times or more of the particle size of
[0347] It should be noted that the imaging range is appropriately selected so that the number of particles is approximately 500.
[0348] In addition, particles with an equivalent circle diameter of less than 0.1 μm are not included in the measurement because their size is too small to have a negligible effect on the performance of the present invention.
[0349] 2. Production of aluminum pigment composition
[0350] Reference Example 1
[0351] A mixture of 50 kg of atomized aluminum powder (average particle size: 25 μm), 82.2 kg of mineral spirits, and 1.5 kg of oleic acid was charged into a ball mill having an inner diameter of 2 m and a length of 30 cm, and ground using 900 kg of steel balls having a diameter of 1.6 mm and a specific gravity of 7.8.
[0352] The steel balls used had a surface roughness of 0.08 μm (grade G40) or less in terms of surface roughness Ra (maximum) of steel balls for ball bearings in accordance with JIS B 1501. The ball mill was rotated at 27 rpm and milling was performed for 6 hours.
[0353] After the grinding, the slurry in the mill was washed with mineral spirits and applied to a 400-mesh vibrating screen. The slurry was then subjected to a hydrocyclone classifier (T-10 SUPERCLONE manufactured by Murata Industries, Ltd.) to remove fine particles of aluminum pigment to 2%.
[0354] The obtained slurry was filtered and concentrated using a filter, and recovered as an aluminum pigment cake. The nonvolatile content was adjusted to obtain an aluminum pigment paste (ie, aluminum flake pigment in a paste form) having a nonvolatile content of 80% by mass.
[0355] Reference Example 2
[0356] The same operation as in Reference Example 1 was carried out except that atomized aluminum powder (average particle size: 20 μm) was used as a raw material to obtain an aluminum pigment paste having a nonvolatile content of 80% by mass.
[0357] Reference Example 3
[0358] The same operation as in Reference Example 1 was carried out except that the fine particles of the aluminum pigment were removed to 9% using a hydrocyclone classifier (manufactured by Murata Industries, Ltd., T-10 SUPERCLONE) to obtain an aluminum pigment paste having a nonvolatile content of 80% by mass.
[0359] Example 1
[0360] There are two inclined paddle-type stirring blades with a blade diameter of 0.5m at positions 0.3m and 0.6m from the bottom surface, with a diameter of 1m and an internal volume of 1m. 2In a reaction tank, 465 kg of methoxypropanol (hereinafter also referred to as "PM") was added to 135 kg of the aluminum pigment paste (average particle size 16 μm, non-volatile content 80% by mass) obtained in Reference Example 1, and the mixture was stirred at 100 rpm (the tip speed of the stirring blade was 2.6 m / sec) by a stirring blade, and the aluminum paste was uniformly dispersed in the PM while returning the dispersion liquid drawn out from the bottom to the upper part of the reaction tank from the reaction tank to the outside circulation. During the external circulation, ultrasonic waves with a frequency of 20 kHz and an output power of 500 W were irradiated for 1 minute in the middle of the flow path to improve the dispersibility of the particles.
[0361] Then, slowly add phosphotungstomolybdic acid (H3PW6Mo6O 40 ) hydrate 1 kg in methoxypropanol 5 kg to prepare a liquid, and the slurry was stirred for 1 hour under the same conditions as above while keeping the slurry temperature at 40°C.
[0362] Then, as an organic silicon compound, 10 kg of tetraethoxysilane was added, and then 10 kg of 25% ammonia water and 200 kg of purified water were added over 3 hours. Then, as a silane coupling agent, 1.3 kg of methyltrimethoxysilane was added, and stirred for 2 hours under the same conditions as above. After the reaction was completed, the slurry was cooled and filtered.
[0363] Thus, an aluminum pigment composition containing 60% of nonvolatile components of composite particles having aluminum metal particles and a coating layer including a silicon compound layer on the surface thereof was obtained. During the reaction, external circulation was continued while irradiating with ultrasonic waves.
[0364] Example 2
[0365] The aluminum pigment paste obtained in Reference Example 2 (average particle size 20 μm, non-volatile component 80% by mass) was changed to the same procedure as in Example 1, thereby obtaining an aluminum pigment composition containing composite particles with a non-volatile component content of 60%, wherein the composite particles have aluminum metal particles and a covering layer comprising a silicon compound layer on their surface.
[0366] Example 3
[0367] The same procedure as in Example 1 was followed except that the amount of tetraethoxysilane was changed to 3 kg, the amount of 25% ammonia water was changed to 3 kg, the amount of purified water was changed to 70 kg, and the amount of methyltrimethoxysilane was changed to 0.5 kg, to obtain an aluminum pigment composition containing composite particles having a non-volatile content of 60%, wherein the composite particles have aluminum metal particles and a covering layer comprising a silicon compound layer on their surface.
[0368] Example 4
[0369] The same procedure as in Example 1 was followed except that the amount of tetraethoxysilane was changed to 50 kg, the amount of 25% ammonia water was changed to 50 kg, the amount of purified water was changed to 500 kg, and the amount of methyltrimethoxysilane was changed to 6.5 kg, and the addition time of ammonia water and purified water was set to 5 hours, to obtain an aluminum pigment composition containing composite particles with a non-volatile content of 60%, wherein the composite particles have aluminum metal particles and a covering layer comprising a silicon compound layer on the surface thereof.
[0370] Example 5
[0371] The aluminum pigment paste obtained in Reference Example 3 (average particle size 20 μm, non-volatile component 80% by mass) was changed to the same procedure as in Example 1, thereby obtaining an aluminum pigment composition containing composite particles with a non-volatile component content of 60%, wherein the composite particles have aluminum metal particles and a covering layer comprising a silicon compound layer on their surface.
[0372] Comparative Example 1
[0373] An aluminum pigment composition having a nonvolatile content of 60% was obtained in the same manner as in Example 1 except that the reaction with the organic silicon compound and the silane coupling agent was not performed.
[0374] Comparative Example 2
[0375] An aluminum pigment composition having a nonvolatile content of 60% was obtained in the same manner as in Example 1 except that the hydrocyclone classifier was not used to remove fine particles.
[0376] Comparative Example 3
[0377] An aluminum pigment composition having a nonvolatile content of 60% was obtained in the same manner as in Example 1 except that one inclined paddle-type stirring blade with a blade diameter of 0.35 m was arranged at a position 0.3 m from the bottom surface, the rotation speed was set to 1500 rpm, and external circulation was not performed.
[0378] Comparative Example 4
[0379] An aluminum pigment composition having a nonvolatile content of 60% was obtained in the same manner as in Example 1 except that tetraethoxysilane was changed to 1.5 kg, 25% ammonia water was changed to 1.5 kg, purified water was changed to 35 kg, and methyltrimethoxysilane was changed to 0.25 kg.
[0380] Comparative Example 5
[0381] The same procedure as in Example 1 was followed except that the amount of tetraethoxysilane was changed to 100 kg, the amount of 25% ammonia water was changed to 100 kg, the amount of purified water was changed to 1000 kg, and the amount of methyltrimethoxysilane was changed to 13 kg, and the addition time of ammonia water and purified water was set to 7 hours, to obtain an aluminum pigment composition having a non-volatile content of 60%.
[0382] The compositions and production conditions of the above-mentioned examples and comparative examples are summarized in Table 1.
[0383] Furthermore, the aluminum pigment compositions obtained in the above-described Examples and Comparative Examples were used to prepare the following coatings, and the coatings were evaluated by the following methods.
[0384] [Table 1]
[0385]
[0386] 3. Manufacture of coatings and coating films
[0387] (1) Manufacturing of coatings
[0388] A water-based metallic paint having the following composition was prepared.
[0389] Aluminum pigment composition: 12.0 g as non-volatile components
[0390] ·Methoxypropanol: 18.0g
[0391] Polyoxyethylene lauryl ether (nonionic surfactant, manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., trade name "ACTINOL L5"): 6.0 g
[0392] Purified water: 12.0g
[0393] · Water-soluble acrylic resin (※1): 110.0g
[0394] Melamine resin (※2): 18.0g
[0395] ※1: Made by Mitsui Chemicals Co., Ltd., Almatex WA911
[0396] *2: Made by Nihon Cytec Industries Inc., Cymel 350
[0397] The aluminum pigment composition used was the aluminum pigment composition obtained in each of Examples and Comparative Examples.
[0398] After mixing the above components, the pH was adjusted to 7.7-7.8 with dimethylethanolamine, and the viscosity was adjusted to 650-750 mPa·s (measured at 25° C. with a B-type viscometer, No. 3 Low, 60 rpm). Thus, a water-based metallic coating was prepared and used for evaluation.
[0399] (2) Manufacturing of coating film
[0400] The water-based metallic paint produced using the above formulation was air-sprayed onto a 12 cm × 6 cm steel plate coated with a mid-coat in a manner to form a dry film thickness of 4 μm. After pre-drying at 90°C for 10 minutes, an organic solvent-based top coating paint was air-sprayed to form a dry film thickness of 20 μm. The coated plate was dried at 140°C for 30 minutes to prepare a coating film for evaluation.
[0401] 4. Evaluation Method
[0402] (1) Evaluation 1 (Paint stability)
[0403] The changes in the state of the water-based metallic coating material for evaluation produced using the above formulation after being left at 23° C. for 24 hours were evaluated with the naked eye as follows.
[0404] ○: No particular change was observed.
[0405] △: Aggregation of some aluminum pigments was observed.
[0406] ×: Aggregation of the aluminum pigment was observed.
[0407] (2) Evaluation 2 (Storage stability (gas generation) evaluation)
[0408] 200 g of the water-based metallic paint prepared by the above formulation was collected in a flask and the cumulative amount of hydrogen gas generated was observed for 24 hours in a constant temperature water bath at 60° C. The amount of gas generated was evaluated as follows as an index of storage stability in the paint.
[0409] ○: less than 5ml
[0410] △: 5ml or more and less than 20ml
[0411] ×: 20ml or more
[0412] (3) Evaluation 3 (Evaluation of coating color tone)
[0413] Using the coating film for evaluation, brightness, color flop (FF), and hiding power were evaluated.
[0414] The organic solvent type surface coating paint was prepared by mixing the following components, dispersing them with a spatula for 3 to 4 minutes, and then adjusting the paint viscosity to 20.0 seconds with a Ford Cup No. 4 to prepare the above surface coating paint.
[0415] ·A345 (DIC Corporation, acrylic transparent resin) 420g
[0416] ·L-117-60 (Melamine resin, manufactured by DIC Corporation) 165g
[0417] · SOLVESSO 100 (Exon Chemical Co., Ltd., aromatic solvent) 228 g
[0418] ·brightness
[0419] The brightness of the coating was evaluated using the laser metal-sensitivity measuring device Alcope LMR-200 manufactured by KANSAIPAINT CO., LTD. As optical conditions, a laser light source with an incident angle of 45 degrees and a light receiver at a receiving angle of 0 degrees and -35 degrees. As a measured value, in addition to the light in the mirror reflection area reflected on the surface of the coating in the reflected light of the laser, the IV value was obtained at a receiving angle of -35 degrees at which the maximum light intensity was obtained. The IV value is a parameter proportional to the intensity of the regular reflected light from the coating, indicating the size of the brightness. The determination method is as described below.
[0420] ○: The decrease from the reference (Comparative Example 1) is less than 20.
[0421] △: The decrease from the reference (Comparative Example 1) is 20 or more and less than 40.
[0422] ×: The decrease from the reference (Comparative Example 1) is 40 or more.
[0423] ·Flip angle (FF)
[0424] The angular colorimeter manufactured by Suga Test Instruments Co., Ltd. was used for evaluation. The FF value was obtained by the slope of the logarithm of the reflected light intensity (L value) at the observation angle (light receiving angle) of 30 degrees and 80 degrees relative to the light source with an incident angle of 45 degrees. The FF value is a parameter proportional to the orientation degree of the metallic pigment, indicating the magnitude of the angular heterochromaticity of the pigment. The determination method is as follows.
[0425] ○: 0.05 or more higher than the reference (Comparative Example 1)
[0426] △: The difference from the reference (Comparative Example 1) is less than ±0.05
[0427] ×: 0.05 or more lower than the reference (Comparative Example 1)
[0428] Concealment
[0429] The produced water-based metallic paint was applied onto a polyethylene terephthalate sheet (PET sheet) using a 2-mil applicator to a dry film thickness of 15 μm, and the coating film dried at 140° C. for 30 minutes was visually evaluated.
[0430] ○: The value is the same as or slightly lower than the reference value (Comparative Example 1).
[0431] △: Decreased compared with the reference (Comparative Example 1).
[0432] ×: Significantly lower than the reference (Comparative Example 1).
[0433] (4) Evaluation 4 (Paint Adhesion / Grid Test)
[0434] Cellotape (registered trademark: CT-24 manufactured by Nichiban Co., Ltd.) was placed in close contact with the coating film for evaluation formed on the coated plate, and pulled at an angle of 45 degrees to visually observe the degree of peeling of the coating film. The evaluation criteria are as follows.
[0435] ○: No peeling
[0436] △: Slight peeling
[0437] ×: Peeling occurs
[0438] The evaluation results are shown in Table 1. It was confirmed that the composite metal pigment of the present invention obtained in each example, which satisfies all of the above physical property conditions (1) to (6), has good stability as a coating, generates little gas (that is, has good storage stability), and also exhibits high brightness, high angle-dependent color, and high hiding power (that is, has good coating color tone), and further has excellent adhesion as a coating film.
[0439] Industrial Applicability
[0440] The composite metal pigment of the present invention and the coating film obtained using the same have excellent design, gloss, suppression of pitting, stability in water-based paint, etc. at a high level beyond the limit of the prior art, and therefore can be suitably used in various applications in which metal pigments have been used so far, such as coatings, inks, and resin kneading agents, more specifically, automobile bodies, automobile repair materials, automobile parts, home appliances, plastic parts, PCM coatings, highly weather-resistant coatings, heat-resistant coatings, corrosion-resistant coatings, ship bottom coatings, offset printing inks, gravure printing inks, screen printing inks, etc., and have high applicability in various fields of industries such as the transportation machinery industry such as automobiles, the electrical and electronic industry such as home appliances, the coating industry, and the printing industry.
Claims
1. A method for producing a metallic pigment composition, comprising: The process of grinding a slurry of metal powder to produce metal particles, and In the step of covering the metal particles with a silicon-containing compound layer, The metal pigment composition contains composite particles, wherein the composite particles have metal particles and one or more covering layers on the surface of the metal particles. (1) The composite particles are in the shape of scales, (2) The volume-based D when the particle size distribution of the composite particles is measured using a laser diffraction particle size analyzer 50 is 3 μm or more and 30 μm or less, (3) the average thickness of the composite particles is 20 nm or more and 300 nm or less, (4) at least one of the covering layers is a silicon compound-containing layer, (5) the ratio of the metal element content based on the metal particles in the composite particles to the silicon content based on the coating layer is 0.02 or more and 0.3 or less in terms of the ratio of the silicon content to the metal element content, (6) the number ratio of the composite particles having a particle size of 0.1 μm or more and 1 μm or less relative to the total number of the composite particles in the metal pigment composition is 10% or less, The method for producing the metallic pigment composition implements at least one of the following: In the grinding process, grinding balls with a mass of 11 mg or less are used; In the grinding step, the ratio of the rotation speed of the grinding device to the critical speed is set to 78% or less; and Prior to the coating step, metal particles with a fine particle size are removed in advance from among the metal particles by classification.
2. The method for producing a metallic pigment composition according to claim 1, wherein: In the grinding process, grinding balls with a mass of 0.08 to 11 mg / piece are used, and the ratio of the rotation speed of the grinding device to the critical rotation speed is 33% to 78%.
3. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: Prior to the coating step, there is further a step of removing metal particles having a fine particle size from the metal particles by classification.
4. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The metal powder is atomized aluminum powder with a particle size of 1 to 30 μm.
5. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: In the grinding step, grinding balls having a specific gravity of 8 or less are used.
6. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The composite particles have a shape factor obtained by dividing the average particle diameter by the average thickness, which is 10 or more and 1500 or less.
7. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The volume-based D when the particle size distribution of the composite particles is measured using a laser diffraction particle size analyzer 50 It is not less than 3 μm and not more than 25 μm.
8. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The volume-based D when the particle size distribution of the composite particles is measured using a laser diffraction particle size analyzer 50 It is 3 μm or more and 20 μm or less.
9. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The average thickness of the composite particles is 20 nm or more and 250 nm or less.
10. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The average thickness of the composite particles is 20 nm or more and 200 nm or less.
11. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: A ratio of a metal element content based on the metal particles in the composite particles to a silicon content based on the covering layer is 0.03 or more and 0.2 or less in terms of a ratio of the silicon content to the metal element content.
12. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: A ratio of a metal element content based on the metal particles in the composite particles to a silicon content based on the covering layer is 0.04 or more and 0.15 or less in terms of a ratio of the silicon content to the metal element content.
13. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The number ratio of the composite particles having a particle diameter of 0.1 μm or more and 1 μm or less in the composite particles is 5% or less relative to the total number of the composite particles in the metal pigment composition.
14. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The number ratio of the composite particles having a particle diameter of 0.1 μm or more and 1 μm or less in the composite particles is 3% or less relative to the total number of the composite particles in the metal pigment composition.
15. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The volume-based D when the particle size distribution of the composite particles is measured using the laser diffraction particle size distribution analyzer. 50 The number ratio of the composite particles having a particle size three times or more of the size of the metal pigment composition is 3% or less relative to the total number of the composite particles in the metal pigment composition.
16. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The volume-based D when the particle size distribution of the composite particles is measured using the laser diffraction particle size distribution analyzer. 50 The number ratio of the composite particles having a particle size three times or more of the size of the metal pigment composition is 1% or less relative to the total number of the composite particles in the metal pigment composition.
17. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The metal particles are aluminum or aluminum alloy. 18 . The method for producing a metallic pigment composition according to claim 1 , wherein the metallic pigment composition further comprises: a covering layer containing at least one of a metal, a metal oxide, a metal hydrate and a resin.
19. The method for producing a metallic pigment composition according to claim 1 or 2, wherein: The silicon compound-containing layer is configured as at least an outermost layer.
20. A method for producing a water-based metallic coating, comprising the step of adding the metallic pigment composition produced by the production method according to any one of claims 1 to 19 to a water-based coating or water-based ink in which a resin as a coating film-forming component is dissolved or dispersed in a medium mainly composed of water.
21. A method for producing a metal coating film, comprising the step of applying an aqueous coating material containing the metal pigment composition produced by the production method according to any one of claims 1 to 19.
Citation Information
Patent Citations
JP1971033239Y1
Heat-sublimable ink ribbon
JP1984079788A
Aluminum pigment, method for producing the same and resin composition
JP2003147226A
Metal pigment composition
JP2019151678A
Aluminum flake pigment and manufacturing method therefor
WO2019077904A1